Positive electrode active material and method for producing the same, positive electrode plate, secondary battery, battery module, battery pack, and power consumption device
A core-shell structured positive active material with crystalline coatings and elemental doping addresses Li/Mn anti-site defects and manganese elution, enhancing the cycle and safety performance of secondary batteries.
Patent Information
- Application Number
- JP2024543172
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2042-07-15
AI Technical Summary
Conventional positive active materials in secondary batteries, such as manganese lithium phosphate, suffer from Li/Mn anti-site defects, manganese elution, and poor cycle and safety performance, leading to reduced energy density and cycle life.
A core-shell structured positive active material is developed, comprising a core of Li1+xMn1-yAyP1-zRzO4 coated with crystalline pyrophosphate and phosphate layers, and a carbon layer, with specific elemental doping to enhance stability and conductivity, and a mixture of stratified and two-dimensional lithium-ion transmission channels.
The solution significantly reduces manganese elution, improves high-temperature cycle performance, cycle stability, and safety, while maintaining or enhancing energy density and rate performance of secondary batteries.
Smart Images

Figure 2025503050000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of secondary batteries, in particular to a positive electrode active material, a method for producing a positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]
[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. As secondary batteries have made great strides in development, their energy density, cycle performance and safety performance are also required to be higher. As a conventional positive electrode active material of secondary batteries, lithium manganese phosphate is prone to Li / Mn antisite defects during charging and discharging, and manganese leaching is relatively serious, which affects the gram capacity of secondary batteries and causes the safety performance and cycle performance of secondary batteries to be poor. Summary of the Invention
[0003] The present application has been made in view of the above-mentioned problems, and aims to provide a positive electrode active material, a method for producing a positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consumption device that solve the problems of low cycle capacity retention rate, short cycle life, and low safety of secondary batteries produced using conventional positive electrode active materials.
[0004] In order to achieve the above object, a first aspect of the present application provides a positive electrode active material, the positive electrode active material including a first positive electrode active material and a second positive electrode active material, The first positive electrode active material is the compound LiNi g Co d Mn e M' fO2, wherein g is selected from the range of 0.314 to 0.970, d is selected from the range of 0 to 0.320, and optionally from the range of 0.047 to 0.320, e is selected from the range of 0.006 to 0.390, the sum of g, d, e and f is 1 and f is greater than 0, M' is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y, and optionally M' is Mg and / or Al; The second positive electrode active material includes a core and a shell covering the core, the shell including a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the core is a compound Li 1+x Mn 1-y A y P 1-z R z O4, and the first coating layer is crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c and the second coating layer comprises a crystalline phosphate X n PO4, and the third coating layer comprises carbon, where x is selected from the range of -0.100 to 0.100, y is selected from the range of 0.001 to 0.909, optionally selected from the range of 0.001 to 0.600, z is selected from the range of 0.001 to 0.100, a is greater than 0 and less than or equal to 2, b is greater than 0 and less than or equal to 4, c is greater than 0 and less than or equal to 3, n is greater than 0 and A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and is optionally one or more elements selected from Fe, V, Ni and Co; R is one or more elements selected from B, Si, N and S, and is optionally one or more elements selected from Si, N and S; and the crystalline pyrophosphate Li a MP2O7 and M b (P2O7) cwherein M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Fe, Co, Ti, and Al; and X is independently one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Li, Fe, Ag, and Al.
[0005] Therefore, the applicant unexpectedly discovered that the second positive electrode active material can be obtained by simultaneously doping the Mn site and the P site of the compound LiMnPO4 with a specific amount of a specific element and coating the surface of the compound with three layers, thereby greatly reducing the elution of manganese and reducing the lattice change rate, and by using it in a secondary battery, it can greatly improve the high-temperature cycle performance, cycle stability, high-temperature storage performance, rate performance, and safety performance of the secondary battery and improve the capacity of the secondary battery. However, since the second positive electrode active material only has a one-dimensional lithium ion transmission channel, while the first positive electrode active material is a layered transition metal oxide and has a two-dimensional lithium ion transmission channel, the present application uses the first positive electrode active material and the second positive electrode active material in combination to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and improve the safety of the secondary battery.
[0006] Unless otherwise noted, the chemical formula is Li 1+x Mn 1-y A y P 1-z R zIn O4, when A is two or more elements, the above-mentioned limit on the numerical range of y is not only a limit on the stoichiometric number of each type of element that is A, but also a limit on the sum of the stoichiometric numbers of each element that is A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers y1, y2...yn of A1, A2...An must each be within the numerical range in which y is limited by this application, and the sum of y1, y2...yn must also be within this numerical range. Similarly, when R is two or more elements, the limit on the numerical range of the stoichiometric numbers of R in this application also has the above meaning. Similarly, a compound of the formula LiNi g Co d Mn e M' f When M' in O2 is two or more elements, the numerical range limitations of the stoichiometric number of M' in this application also have the above meaning.
[0007] In this specification, crystallinity refers to a degree of crystallinity of 50% or more, i.e., 50% to 100%. A degree of crystallinity less than 50% is called a glass state. The degree of crystallinity of the crystalline pyrophosphate and crystalline phosphate of the present application is 50% to 100%. Pyrophosphate and phosphate with a certain degree of crystallinity are not only advantageous for the pyrophosphate coating layer to inhibit the elution of manganese and to fully exert the excellent lithium ion conducting ability and the function of reducing the interfacial side reaction of the phosphate coating layer, but also can achieve better lattice matching between the pyrophosphate coating layer and the phosphate coating layer, thereby realizing a tight bond between the coating layers.
[0008] In any embodiment, the mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the value of m1 / (m1+m2) is 2% to 55%, and optionally 3% to 50%, such that the mass percentage of the first positive electrode active material in the two positive electrode active materials is within the above range, and the stability and safety of the entire positive electrode active material can be improved.
[0009] In any of the embodiments, the value of g×m1 / (m1+m2) is 0.017 to 0.457, and optionally 0.025 to 0.415, thereby making it possible to further improve the stability and safety of the entire positive electrode active material.
[0010] In any of the embodiments, the first positive electrode active material is a single crystal or pseudo-single crystal material, and the particle size D of the first positive electrode active material is v 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and more preferably 2.3 to 4.3 μm.
[0011] By setting the particle size of the single crystal or pseudo-single crystal first positive electrode active material within the above range, the area of the electrochemical reaction can be optimized, and the interfacial side reaction of the positive electrode during the secondary battery cycle can be further reduced and suppressed, thereby reducing the cycle decay rate of the secondary battery and extending the cycle life of the secondary battery.
[0012] In any embodiment, when the first cathode active material is a single crystal or pseudo single crystal material, d is selected from the range of 0.047 to 0.320, optionally selected from the range of 0.047 to 0.235, and / or b is greater than 0.314 and less than 0.97, and is selectively selected within the range of 0.55 to 0.869.
[0013] When the first positive electrode active material is a single crystal or pseudo-single crystal material, d and b within the above ranges are advantageous for further improving the conductivity and rate performance of the positive electrode active material, further improving the cycle capacity retention rate of the secondary battery, and further extending the cycle life of the secondary battery.
[0014] In any of the embodiments, the first positive electrode active material is a polycrystalline material, and the particle size D of the first positive electrode active material is v 50 is 3.0 to 13.5 μm, optionally 3.5 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and selectively 1.32m 2 / g or less, and more selectively, 0.28 to 1.32 m 2 / g, and / or The first positive electrode active material has a compacted density of 2.90 g / cm at a pressure of 3 T. 3 or more, and optionally 2.92 g / cm 3 or more, more selectively, 2.92 to 3.31 g / cm 3 It is.
[0015] By setting the particle size, specific surface area and compaction density of the polycrystalline first positive electrode active material within the above ranges, the rate performance of the positive electrode active material can be further improved, the interfacial side reaction of the positive electrode during secondary battery cycling can be further reduced and suppressed, the cycle decay rate of the secondary battery can be reduced, and the cycle life of the secondary battery can be extended.
[0016] In any embodiment, the first positive electrode active material further comprises lithium carbonate and / or lithium hydroxide; Optionally, based on the mass of the first positive electrode active material, the mass content of lithium carbonate is 1.05% or less, optionally 1% or less, and / or the mass content of lithium hydroxide is 1.02% or less, optionally 1% or less.
[0017] Residual water molecules captured in the second positive electrode active material may react with the electrolyte to generate HF, which is likely to cause damage to the positive electrode active material itself or the SEI film on the negative electrode plate, and further affect the life of the secondary battery. The lithium carbonate and / or lithium hydroxide further contained in the first positive electrode active material of the present application can undergo a neutralization reaction with HF, reducing or suppressing the damage caused by HF to the positive electrode active material or the SEI film on the negative electrode plate, thereby further improving the cycle life of the secondary battery.
[0018] In any one of the embodiments, in the second positive electrode active material, the crystal plane spacing range of the crystalline pyrophosphate in the first coating layer is 0.293 to 0.470 nm, and optionally 0.303 to 0.462 nm, and the angle range of the crystal orientation (111) is 18.00° to 32.00°, and optionally 19.211° to 30.846°, and / or The crystal plane spacing range of the crystalline phosphate in the second coating layer is 0.244 to 0.425 nm, and the angle range of the crystal orientation (111) is 20.00° to 37.00°, and optionally 20.885° to 36.808°.
[0019] The first and second coating layers in the second positive electrode active material of the present application are both made of crystalline materials, and the angle range between the crystal plane spacing and the coating layers is within the above range, which can effectively avoid impurity phases in the coating layers, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery.
[0020] In any embodiment, in the core of the second positive electrode active material, the ratio of y to 1-y is 1:10 to 10:1, and optionally 1:4 to 1:1, where y represents the sum of the stoichiometric numbers of elements doped into the Mn site. When the above conditions are met, the energy density, cycle performance and rate performance of the manufactured secondary battery can be further improved.
[0021] In any embodiment, in the core of the second positive electrode active material, the ratio of z to 1-z is 1:999 to 1:9, and optionally 1:499 to 1:249, where z represents the sum of the stoichiometric numbers of the elements doped in the P site. When the above condition is satisfied, the energy density, cycle performance and rate performance of the manufactured secondary battery can be further improved.
[0022] In any embodiment, in the second positive electrode active material, the carbon in the third coating layer is a mixture of SP2 form carbon and SP3 form carbon; Alternatively, the molar ratio of carbon in the SP2 form to carbon in the SP3 form is between 0.1 and 10, and more preferably between 2.0 and 3.0.
[0023] In the present application, the molar ratio of SP2 form carbon to SP3 form carbon is limited within the above range, thereby improving the overall performance of the secondary battery.
[0024] In any embodiment, in the second positive electrode active material, the coating amount of the first coating layer is greater than 0 and less than 6 wt %, optionally greater than 0 and less than 5.5 wt %, and further optionally greater than 0 and less than 2 wt %, based on the weight of the core; and / or The amount of the second coating layer is, based on the weight of the core, greater than 0 and not greater than 6 wt%, optionally greater than 0 and not greater than 5.5 wt%, and further optionally 2 to 4 wt%, and / or The coverage of the third coating layer is, based on the weight of the core, greater than 0 and not greater than 6 wt%, optionally greater than 0 and not greater than 5.5 wt%, and further optionally greater than 0 and not greater than 2 wt%.
[0025] In the second positive electrode active material having a core-shell structure of the present application, the coating amount of the three coating layers is preferably within the above range, so that the core can be sufficiently coated, and at the same time, the gram capacity of the second positive electrode active material is not sacrificed, and the dynamic performance and safety performance of the secondary battery are further improved.
[0026] In any embodiment, in the second positive electrode active material, the first coating layer has a thickness of 1 to 10 nm, and / or the thickness of the second coating layer is between 2 and 15 nm, optionally between 2.5 and 7.5 nm; and / or The third covering layer has a thickness of 2 to 25 nm.
[0027] In the present application, when the thickness range of the first coating layer is 1-10 nm, it is possible to avoid the adverse effect on the dynamic performance of the material that may occur when the first coating layer is too thick, and to avoid the problem of not being able to effectively inhibit the transition of transition metal ions when the first coating layer is too thin. When the thickness of the second coating layer is within the above range, the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so that the interface side reaction can be effectively reduced, thereby improving the high temperature performance of the secondary battery. When the thickness range of the third coating layer is 2-25 nm, it is possible to increase the electrical conductivity performance of the material and improve the compaction density performance of the battery plate manufactured using the second positive electrode active material.
[0028] In any embodiment, the content of elemental manganese is in the range of 10 wt% to 35 wt%, alternatively in the range of 15 wt% to 30 wt%, and further alternatively in the range of 17 wt% to 20 wt%, based on the weight of the second positive electrode active material; and / or The content of phosphorus element is in the range of 12% by weight to 25% by weight, and optionally in the range of 15% by weight to 20% by weight, and / or The weight ratio range of elemental manganese to elemental phosphorus is 0.90-1.25, and optionally 0.95-1.20.
[0029] In the second positive electrode active material having a core-shell structure of the present application, the manganese content within the above range can effectively avoid problems such as poor stability of material structure and reduced density that may occur when the manganese content is too high, thereby improving the performance of the secondary battery in terms of cycle, storage and compaction density, etc., and can avoid problems such as low voltage plateau that may occur when the manganese content is too low, thereby improving the energy density of the secondary battery.
[0030] In the second positive electrode active material having a core-shell structure of the present application, the content of phosphorus within the above range can effectively avoid the following situation: if the content of phosphorus is too large, the covalent bond of PO is too strong, which may affect the conductivity of small polaritons, thereby affecting the conductivity of the material; if the content of phosphorus is too small, the stability of the core, the pyrophosphate in the first coating layer and / or the phosphate lattice structure in the second coating layer may be reduced, thereby affecting the stability of the entire material.
[0031] In the second positive electrode active material having a core-shell structure of the present application, the weight ratio of elemental manganese and elemental phosphorus being within the above range can effectively avoid the following situation: if this weight ratio is too large, the leaching of transition metals will increase, which may affect the stability of the material and the cycle and storage performance of the secondary battery; if this weight ratio is too small, the discharge voltage plateau of the material will decrease, thereby reducing the energy density of the secondary battery.
[0032] In any embodiment, the lattice change rate of the second positive electrode active material before and after complete release of lithium is 4% or less, optionally 3.8% or less, and further optionally 2.0 to 3.8%.
[0033] The second positive electrode active material having a core-shell structure of the present application can realize a lattice change rate of 4% or less before and after releasing lithium. Therefore, by using the second positive electrode active material, the gram capacity and rate performance of the secondary battery can be improved.
[0034] In any of the embodiments, the Li / Mn antisite defect concentration of the second positive electrode active material is 4% or less, optionally 2.2% or less, and further optionally 1.5 to 2.2%. By setting the Li / Mn antisite defect concentration within the above range, Mn 2+ Li + This avoids impeding the transmission of the charge and increases the gram capacity of the second positive electrode active material and the rate performance of the secondary battery.
[0035] In any embodiment, the second positive electrode active material has a packed density at 3 T of 2.2 g / cm 3 or more, and optionally 2.2 g / cm 3 Above 2.8g / cm 3 The higher the compaction density of the second positive electrode active material, that is, the larger the weight of the active material per unit volume, the more advantageous it is for increasing the volumetric energy density of the secondary battery.
[0036] In any of the embodiments, the surface oxygen valence of the second positive electrode active material is -1.90 or less, and optionally -1.90 to -1.98. This is because the higher the valence of the oxygen compound, the stronger its ability to obtain electrons, i.e., the stronger its oxidizing property. Thus, by limiting the surface oxygen valence of the first positive electrode active material within the above range as described above, it is possible to reduce the interfacial side reaction between the first positive electrode active material and the electrolyte, thereby improving the performance of the cell in terms of cycle, high-temperature storage, gas generation, etc.
[0037] A second aspect of the present application further provides a method for producing a cathode active material, the method comprising: providing a first active cathode material and a second active cathode material; mixing a first positive electrode active material with a second positive electrode active material; The first positive electrode active material is the compound LiNi g Co d Mn e M' f O2, the second positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the core is a compound Li 1+x Mn 1-y A y P 1-z R z O4, and the first coating layer is crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) cand the second coating layer comprises a crystalline phosphate X n PO4, and the third coating layer comprises carbon, wherein the definitions of g, d, e, f, x, y, z, a, b, c, n, A, R, M, X and M' are as described in the first aspect of the present application; Optionally, the first positive electrode active material further includes lithium carbonate and / or lithium hydroxide.
[0038] As a result, the present application uses a mixture of a first positive electrode active material and a second positive electrode active material to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and enhance the safety of the secondary battery.
[0039] A third aspect of the present application provides a positive electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the method of the second aspect of the present application, and optionally, the content of the positive electrode active material in the positive electrode film layer is 10 wt % or more, and further optionally, 95 to 99.5 wt %, based on the total weight of the positive electrode film layer.
[0040] A fourth aspect of the present application provides a secondary battery, the secondary battery comprising the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0041] A fifth aspect of the present application provides a battery module, the battery module including the secondary battery of the fourth aspect of the present application.
[0042] A sixth aspect of the present application provides a battery pack, the battery pack including the battery module of the fifth aspect of the present application.
[0043] A seventh aspect of the present application provides a power consumption device, the power consumption device including at least one selected from a secondary battery of the fourth aspect of the present application, a battery module of the fifth aspect of the present application, and a battery pack of the sixth aspect of the present application. [Brief description of the drawings]
[0044] [Figure 1] FIG. 2 is a schematic diagram of a second positive electrode active material having a core-shell structure according to one embodiment of the present application. [Diagram 2] 1 is a schematic diagram of a secondary battery according to one embodiment of the present application. [Diagram 3] FIG. 3 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG. 2. [Figure 4] FIG. 1 is a schematic diagram of a battery module according to one embodiment of the present application. [Diagram 5] 1 is a schematic diagram of a battery pack according to one embodiment of the present application. [Figure 6] FIG. 6 is an exploded view of the battery pack shown in FIG. 5 according to one embodiment of the present application. [Figure 7] 1 is a schematic diagram of a power consuming device that uses a secondary battery as a power source according to one embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] Hereinafter, with reference to the drawings, embodiments specifically disclosing the positive electrode active material, the method for manufacturing the positive electrode active material, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and do not limit the subject matter described in the claims.
[0046] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the bounds, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as the minimum range values, and 3, 4, and 5 are listed as the maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, a numerical range "a-b" represents a shorthand representation of any combination of real numbers a-b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is merely a shorthand for combinations of these numbers. Also, a statement that a parameter is an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0047] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0048] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0049] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, but are preferably performed in sequence. For example, a method includes steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, a method may further include step (c) means that step (c) may be added to the method in any order, such as the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0050] Unless otherwise stated, the terms "comprise" and "comprises" referred to in this application are open ended but may also be closed ended. For example, "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0051] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition where A is true (or exists) and B is false (or does not exist), the condition where A is false (or does not exist) but B is true (or exists), and the condition where both A and B are true (or exist) all satisfy "A or B."
[0052] Unless otherwise specified, in this application, the median particle size Dv 50 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%. In this application, the median particle size D v 50 can be measured using laser diffraction particle size analysis, for example, see standard GB / T 19077-2016, using a laser particle size analyzer (e.g., Malvern Master Size 3000).
[0053] Unless otherwise stated, in this application, the term "coating layer" refers to a layer of material coated on a core, the layer of material may completely or partially cover the core, and the term "coating layer" is used merely for ease of description and is not intended to limit the present invention. Similarly, the term "thickness of the coating layer" refers to the thickness of the layer of material coated on the core in the radial direction of the core.
[0054] Unless otherwise specified, in this application, the term "source" refers to a compound that is a source of an element, and illustrative types of "source" include, but are not limited to, carbonates, sulfates, nitrates, elements, halides, oxides and hydroxides.
[0055] [Secondary battery] A secondary battery is also called a rechargeable battery or storage battery, and is a battery that can be continuously used by activating the active material through charging after the battery is discharged.
[0056] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During charging and discharging of the battery, active ions (e.g., lithium ions) shuttle between the positive electrode plate and the negative electrode plate to absorb and release. The separator is disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short-circuiting between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte mainly serves to conduct the active ions between the positive electrode plate and the negative electrode plate.
[0057] [Cathode active material] One embodiment of the present application provides a cathode active material, the cathode active material comprising a first cathode active material and a second cathode active material, wherein: The first positive electrode active material is the compound LiNi g Co d Mn e M' fO2, wherein g is selected from the range of 0.314 to 0.970, and optionally from the range of 0.550 to 0.970; d is selected from the range of 0 to 0.320, and optionally from the range of 0.047 to 0.320, or 0.005 to 0.188; e is selected from the range of 0.006 to 0.390, and optionally from the range of 0.006 to 0.249; the sum of g, d, e and f is 1 and f is greater than 0; M' is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y, and optionally M' is Mg and / or Al; The second positive electrode active material includes a core and a shell covering the core, the shell including a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the core is a compound Li 1+x Mn 1-y A y P 1-z R z O4, and the first coating layer is crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c and the second coating layer comprises a crystalline phosphate X nPO4, and the third coating layer comprises carbon, where x is selected from the range of -0.100 to 0.100, y is selected from the range of 0.001 to 0.909, and optionally selected from the range of 0.001 to 0.600, z is selected from the range of 0.001 to 0.100, a is greater than 0 and less than or equal to 2, b is greater than 0 and less than or equal to 4, and optionally selected from the range of 1 to 4, c is greater than 0 and less than or equal to 3, and optionally selected from the range of 1 to 3, n is greater than 0 and less than or equal to 1, is at most 3 and is optionally selected from the range of 1 to 3 (e.g., 1, 2, 3); A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, optionally one or more elements of Fe, V, Ni, and Co; R is one or more elements selected from B (boron), Si, N, and S, optionally one or more elements selected from Si, N, and S; and the crystalline pyrophosphate Li a MP2O7 and M b (P2O7) c wherein M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Fe, Co, Ti, and Al, and further optionally one or more elements selected from Fe, Ti, and Al; and X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Li, Fe, Co, Ag, and Al.
[0058] The first positive electrode active material is a layered transition metal oxide, which has a two-dimensional lithium ion transmission channel, and the second positive electrode active material only has a one-dimensional lithium ion transmission channel. The first positive electrode active material generally has a lower initial clone efficiency than the second positive electrode active material. The first positive electrode active material is generally used in combination with the second positive electrode active material. The first positive electrode active material is generally used in combination with the second positive electrode active material. The first positive electrode active material generally has a lower initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the second positive electrode active material. The second positive electrode active material generally has a higher initial clone efficiency than the first ... first positive electrode active material. The second positive electrode active material generally has
[0059] In addition, although the mechanism is not yet clear, the applicant believes that the second positive electrode active material of the present application has a core-shell structure, in which the manganese site and phosphorus site of the lithium manganese phosphate core are doped with element A and element R, respectively, thereby effectively reducing the elution of manganese, further reducing the manganese ions transferred to the negative electrode, reducing the electrolyte consumed by the decomposition of the SEI film, and improving the cycle performance and safety performance of the secondary battery. It can also promote the adjustment of Mn-O bonds, reduce the transition barrier of lithium ions, promote the transition of lithium ions, and improve the rate performance of the secondary battery. The first coating layer containing crystalline pyrophosphate is a core-shell structure. By coating the second positive electrode active material with a crystalline phosphate coating layer having excellent lithium ion conductivity, the interfacial side reaction on the surface of the second positive electrode active material can be effectively reduced, and the high-temperature cycle and storage performance of the secondary battery can be further improved. By further coating a carbon layer as a third coating layer, the safety performance and dynamic performance of the secondary battery can be further improved. It was also unexpectedly discovered that in the core, element A doped into the manganese site of lithium manganese phosphate reduces the lattice change rate of lithium manganese phosphate during the lithium release of this material, improves the structural stability of the second positive electrode active material, significantly reduces the dissolution of manganese, and also contributes to reducing the oxygen activity of the particle surface; and element R doped into the phosphorus site also contributes to changing the difficulty of changing the Mn-O bond length, thereby improving electronic conductivity and reducing the transition barrier of lithium ions, promoting the transition of lithium ions, and improving the rate performance of the secondary battery.
[0060] In some embodiments, M' is Mg and / or Al. Doping the first positive electrode active material with Al element can increase the structural stability and thermal stability of the material and improve the cycle performance; doping the first positive electrode active material with Mg element can increase or decrease the transition metal ion valence, thereby generating holes or electrons, changing the band structure of the material, improving the intrinsic electronic conductivity of the material, and improving the cycle performance of the secondary battery; co-doping Mg and Al into the lattice of the main body material can synergistically stabilize the material structure, improve the miscibility of the material cations, inhibit oxygen precipitation, and further improve the cycle performance and thermal stability of the secondary battery.
[0061] Unless otherwise noted, the chemical formula is Li 1+x Mn 1-y A y P 1-z R z In O4, when A is two or more elements, the above-mentioned limit on the y range is not only a limit on the stoichiometric number of each type of element that is A, but also a limit on the sum of the stoichiometric numbers of each element that is A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers y1, y2...yn of A1, A2...An must each be within the numerical range in which y is limited by this application, and the sum of y1, y2...yn must also be within this numerical range. Similarly, when R is two or more elements, the limit on the numerical range of the stoichiometric number of R in this application also has the above meaning. Similarly, a compound of the chemical formula LiNi g Co d Mn e M' f When M' in O2 is two or more elements, the numerical range limitations of the stoichiometric number of M' in this application also have the above meaning.
[0062] In some embodiments, in the second active cathode material, when A is one, two, three, or four elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, A y Q n1 D n2 En3 K n4 where n1+n2+n3+n4=y, and n1, n2, n3, n4 are all positive numbers and not zero at the same time, and Q, D, E, and K are each independently one selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally at least one of Q, D, E, and K is Fe. Optionally, one of n1, n2, n3, and n4 is zero and the remaining is not zero, and further optionally, two of n1, n2, n3, and n4 are zero and the remaining is not zero, and further optionally, three of n1, n2, n3, and n4 are zero and the remaining is not zero. Core Li 1+x Mn 1-y A y P 1-z R z In O4, it is advantageous to dope the manganese site with one, two, three or four of the above A elements, and selectively dope the phosphorus site with one, two or three of the above A elements, and it is advantageous to dope the phosphorus site with one or two R elements, thus making the doping elements uniformly distributed.
[0063] In some embodiments, in the second active cathode material, the values of x, y, and z satisfy the condition for maintaining electrical neutrality throughout the core.
[0064] In some embodiments, the second positive electrode active material comprises a core Li 1+x Mn 1-y A y P 1-z R zIn O4, the magnitude of x is influenced by the magnitude of the valence of A and R and the magnitude of y and z, and ensures that the whole system exhibits electrical neutrality. If the value of x is too small, it will reduce the lithium content of the whole core system, affecting the gram capacity of the material. The value of y limits the total amount of all doping elements, and if y is too small, that is, if the doping amount is too small, the doping element will not function, and if y is more than 0.6, the content of Mn in the system will be low, which will affect the voltage plateau of the material. The R element is doped at the P position, and the PO tetrahedron is relatively stable, but if the z value is too large, it will affect the stability of the material, so the z value is limited to 0.001 to 0.100.
[0065] In addition, maintaining the electrical neutrality of the entire core system can ensure that defects and heterophases in the second positive electrode active material are minimized. If an excess transition metal (e.g., manganese) is present in the second positive electrode active material, the structure of the material system itself is relatively stable, so that the excess transition metal is likely to precipitate in the form of an element or form a heterophase inside the lattice, and by maintaining electrical neutrality, such heterophases can be minimized. In addition, ensuring the electrical neutrality of the system can also improve the kinetic performance of the material by generating lithium vacancies in the material in some cases.
[0066] In some embodiments, the values of a, b, and c in the second active cathode material are selected from the group consisting of crystalline pyrophosphate Li a MP2O7 or M b (P2O7) c The condition of maintaining electrical neutrality is met.
[0067] In some embodiments, the crystallinity refers to a degree of crystallinity of 50% or more, i.e., 50% to 100%. A degree of crystallinity less than 50% is called a glass state. The crystallinity of the crystalline pyrophosphate and crystalline phosphate of the present application is 50% to 100%. Pyrophosphates and phosphates with a certain degree of crystallinity are not only advantageous for the pyrophosphate coating layer to inhibit the elution of manganese and to fully exert the excellent lithium ion conducting ability and the function of reducing the interfacial side reaction of the phosphate coating layer, but also can achieve better lattice matching between the pyrophosphate coating layer and the phosphate coating layer, thereby realizing a tighter bond between the coating layers.
[0068] In some embodiments, the crystallinity of the crystalline pyrophosphate of the first coating layer material and the crystalline phosphate of the second coating layer material of the second positive electrode active material may be tested by common technical means in the art, such as by density method, infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance spectroscopy, and may also be tested by, for example, X-ray diffraction method.
[0069] A specific method for testing the crystallinity of the first coating layer crystalline pyrophosphate and the second coating layer crystalline phosphate of the second positive electrode active material by X-ray diffraction may include the following steps.
[0070] A certain amount of the second positive electrode active material powder is taken, and the total scattering intensity is measured by X-ray, which is the sum of the scattering intensity of the material in the entire space, and has nothing to do with the order state of the sample, but only with the intensity of the primary radiation, the chemical structure of the second positive electrode active material powder, and the total number of electrons involved in diffraction, i.e., the amount of mass. Crystalline scattering and non-crystalline scattering are separated from the diffraction pattern, and the crystallinity is the ratio of the crystalline partial scattering to the total scattering intensity.
[0071] It should be noted that the crystallinity of the pyrophosphate and phosphate in the coating layer can be adjusted, for example, by adjusting the process conditions of the sintering process, such as sintering temperature, sintering time, and so on.
[0072] In the second positive electrode active material, since metal ions are unlikely to transition through pyrophosphate, the doped metal ions can be effectively isolated from the electrolyte by using pyrophosphate as the first coating layer. Since the structure of crystalline pyrophosphate is stable, the elution of transition metals can be effectively suppressed by coating the crystalline pyrophosphate, and cycle performance can be improved.
[0073] In the second positive electrode active material, the bond between the first coating layer and the core is similar to a hetero bond, and the strength of the bond is limited by the degree of lattice matching. When the lattice mismatch is 5% or less, the lattice matching is relatively good and the two are easily bonded tightly. The tight bond can ensure that the coating layer does not fall off during subsequent cycles, which is favorable for ensuring the long-term stability of the material. The degree of bond between the first coating layer and the core is mainly evaluated by calculating the degree of mismatch between the core and the constants that coat each lattice. In the present application, by doping the core with A and R elements, the degree of matching between the core and the first coating layer is improved compared to not doping the elements, and the core and the pyrophosphate coating layer can be bonded more tightly.
[0074] In the second positive electrode active material, the crystalline phosphate is selected as the second coating layer because, first, it has a relatively high lattice match with the crystalline pyrophosphate, which is the coating of the first layer (mismatch is only 3%), and second, the stability of the phosphate itself is better than that of pyrophosphate, so coating with pyrophosphate is advantageous for improving the stability of the material. Since the structure of the crystalline phosphate is very stable and it has excellent lithium ion conductivity, the coating with the crystalline phosphate can effectively reduce the interfacial side reaction on the surface of the second positive electrode active material, thereby improving the high-temperature cycle and storage performance of the secondary battery. The lattice matching manner between the second coating layer and the first coating layer is similar to the bonding situation between the first coating layer and the core, and when the lattice mismatch is 5% or less, the lattice matching is relatively good and the two are easily bonded closely.
[0075] The main reason for coating the second positive electrode active material with carbon as the third layer is that the carbon layer has relatively good electronic conductivity. When applied to a secondary battery, an electrochemical reaction occurs, which requires the involvement of electrons, so that the carbon layer can be coated with carbon having excellent electrical conductivity to increase the electronic transmission between particles and between different positions on the particles. The carbon coating can effectively improve the electrical conductivity and desolvation ability of the second positive electrode active material.
[0076] FIG. 1 is a schematic diagram of a second positive electrode active material with an ideal three-layer coating structure. As shown in the figure, the innermost circle is a schematic representation of a core, and from the inside, the first coating layer, the second coating layer, and the third coating layer are arranged. This figure represents an ideal state in which each layer is completely coated, and in practice, each coating layer may be completely or partially coated.
[0077] In some embodiments, the compound LiNi b Co d Mn e M' f O2 maintains electroneutrality.
[0078] In some embodiments, the mass of the first positive electrode active material is m1, the mass of the second positive electrode active material is m2, and the value of m1 / (m1+m2) is 2%-55%, optionally 3%-50%, such that the mass percentage of the first positive electrode active material in the two positive electrode active materials is within the above range, and the stability and safety of the entire positive electrode active material can be improved.
[0079] In some embodiments, the value of g×m1 / (m1+m2) is 0.017 to 0.457, and optionally 0.025 to 0.415, thereby further improving the stability and safety of the entire positive electrode active material.
[0080] In some embodiments, the first active cathode material is a single crystal or pseudo-single crystal material, and the particle size D of the first active cathode material is v50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and more preferably 2.3 to 4.3 μm.
[0081] By setting the particle size of the single crystal or pseudo-single crystal first positive electrode active material within the above range, the area of the electrochemical reaction can be optimized, and the interfacial side reaction of the positive electrode during the secondary battery cycle can be further reduced and suppressed, thereby reducing the cycle decay rate of the secondary battery and extending the cycle life of the secondary battery.
[0082] In some embodiments, when the first active cathode material is a single crystal or pseudo single crystal material, d is selected from the range of 0.047 to 0.320, optionally selected from the range of 0.047 to 0.235, and / or b is greater than 0.314 and less than 0.97, and is selectively selected within the range of 0.55 to 0.869.
[0083] When the first positive electrode active material is a single crystal or pseudo-single crystal material, d and b within the above ranges are advantageous for further improving the conductivity and rate performance of the positive electrode active material, further improving the cycle capacity retention rate of the secondary battery, and further extending the cycle life of the secondary battery.
[0084] In some embodiments, the first active cathode material is a polycrystalline material, and the particle size D of the first active cathode material is v 50 is 3.0 to 13.5 μm, optionally 3.5 to 13.5 μm, and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and selectively 1.32m 2 / g or less, and more selectively, 0.28 to 1.32 m 2 / g, and / or The first positive electrode active material has a compacted density of 2.90 g / cm at a pressure of 3 T. 3 or more, and optionally 2.92 g / cm 3 or more, more selectively, 2.92 to 3.31 g / cm 3 It is.
[0085] By setting the particle size, specific surface area and compaction density of the polycrystalline first positive electrode active material within the above ranges, the rate performance of the positive electrode active material can be further improved, the interfacial side reaction of the positive electrode during secondary battery cycling can be further reduced and suppressed, the cycle decay rate of the secondary battery can be reduced, and the cycle life of the secondary battery can be extended.
[0086] In some embodiments, the first active cathode material further comprises lithium carbonate and / or lithium hydroxide; Optionally, based on the mass of the first positive electrode active material, the mass content of lithium carbonate is 1.05% or less, optionally 1% or less, and / or the mass content of lithium hydroxide is 1.02% or less, optionally 1% or less.
[0087] Residual water molecules captured in the second positive electrode active material may react with the electrolyte to generate HF, which is likely to cause damage to the positive electrode active material itself or the SEI film on the negative electrode plate, and further affect the life of the secondary battery. The lithium carbonate and / or lithium hydroxide further contained in the first positive electrode active material of the present application can undergo a neutralization reaction with HF, reducing or suppressing the damage caused by HF to the positive electrode active material or the SEI film on the negative electrode plate, thereby further improving the cycle life of the secondary battery.
[0088] In some embodiments, in the second positive electrode active material, the crystal plane spacing range of the crystalline pyrophosphate in the first coating layer is 0.293 to 0.470 nm, and optionally 0.303 to 0.462 nm; the angle range of the crystal orientation (111) is 18.00° to 32.00°, and optionally 19.211° to 30.846°; and / or The crystal plane spacing range of the crystalline phosphate in the second coating layer is 0.244 to 0.425 nm, and the angle range of the crystal orientation (111) is 20.00° to 37.00°, and optionally 20.885° to 36.808°.
[0089] The first and second coating layers in the second positive electrode active material of the present application both use crystalline materials, and the angle range between the crystal plane spacing and the coating layers is within the above range. This can effectively avoid impurity phases in the coating layers, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery. The crystalline pyrophosphate and crystalline phosphate in the coating layers can be characterized by common technical means in the art, for example, by transmission electron microscopy (TEM). In the TEM, the core and the coating layers can be distinguished by examining the crystal plane spacing.
[0090] A specific method for testing the angle between the crystal plane spacing of the crystalline pyrophosphate and the crystalline phosphate in the coating layer may include the following steps.
[0091] A certain amount of the coated second positive electrode active material sample powder is placed in a test tube, and a solvent, such as alcohol, is poured into the test tube and thoroughly stirred to disperse it. Then, an appropriate amount of the above solution is taken with a clean disposable plastic straw and dropped onto a 300 mesh copper net, at this time, some of the powder remains on the copper net, and the copper net together with the sample is transferred to the TEM sample cavity for testing, and the original image of the TEM test is obtained and preserved.
[0092] The original image obtained in the above TEM test is opened in the diffractometer software and Fourier transformed to obtain a diffraction pattern. The distance from the diffraction spot to the center position in the diffraction pattern is measured to obtain the crystal plane spacing, and the angle formed is calculated using the Bragg equation.
[0093] The difference between the range of crystal plane spacing of crystalline pyrophosphate and that of crystalline phosphate can be directly determined by the numerical value of the crystal plane spacing.
[0094] In some embodiments, in the core of the second positive electrode active material, the ratio of y to 1-y is 1:10 to 10:1, and optionally 1:4 to 1:1, where y represents the sum of the stoichiometric numbers of elements doped into the Mn site. When the above conditions are met, the energy density, cycle performance and rate performance of the manufactured secondary battery can be further improved.
[0095] In some embodiments, in the core of the second positive electrode active material, the ratio of z to 1-z is 1:999 to 1:9, and optionally 1:499 to 1:249, where z represents the sum of the stoichiometric numbers of the elements doped in the P site. When the above condition is satisfied, the energy density, cycle performance and rate performance of the manufactured secondary battery can be further improved.
[0096] In some embodiments, in the second positive electrode active material, the carbon in the third coating layer is a mixture of SP2 and SP3 carbon forms; Alternatively, the molar ratio of carbon in the SP2 form to carbon in the SP3 form is between 0.1 and 10, and more preferably between 2.0 and 3.0.
[0097] In some embodiments, the molar ratio of carbon in the SP2 form to carbon in the SP3 form can be about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10, or any range within any of the above values.
[0098] In this application, the term "about" a certain value denotes a range, representing a range of ±10% of that value.
[0099] By selecting the form of carbon in the carbon coating layer, the overall electrical performance of the secondary battery is improved. Specifically, by using a mixed form of SP2 carbon and SP3 carbon and limiting the ratio of SP2 carbon to SP3 carbon within a certain range, the following situation can be avoided: when the carbon in the coating layer is all amorphous SP3 form, the electrical conductivity is poor, and when all are graphitized SP2 form, the electrical conductivity is good but the lithium ion channel is small, which is unfavorable for lithium release. In addition, by limiting the molar ratio of SP2 carbon to SP3 carbon within the above range, good electrical conductivity can be achieved and the lithium ion channel can be guaranteed, which is favorable for the realization of secondary battery function and its cycle performance.
[0100] The mixture ratio of the SP2 form and the SP3 form of the carbon in the third coating layer can be controlled by the sintering conditions, such as the sintering temperature and the sintering time. For example, when the third coating layer is produced using sucrose as a carbon source, the sucrose is cleaved at high temperature, and then deposited on the second coating layer, and at the same time, a carbon coating layer having both SP3 form and SP2 form is generated by the action of high temperature. The ratio of the SP2 form carbon and the SP3 form carbon can be controlled by selecting the high-temperature cleavage conditions and the sintering conditions.
[0101] The structure and characteristics of the third coating carbon can be measured by Raman spectroscopy. A specific test method is to perform peak splitting on the spectrum of the Raman test to obtain Id / Ig (where Id is the peak intensity of the SP3 carbon form and Ig is the peak intensity of the SP2 carbon form), thereby determining the molar ratio of the two.
[0102] In some embodiments, in the second positive electrode active material, the coverage of the first coating layer is greater than 0 and less than 6 wt %, optionally greater than 0 and less than 5.5 wt %, and further optionally greater than 0 and less than 2 wt %, for example 1%, based on the weight of the core; and / or The amount of the second coating layer is, based on the weight of the core, greater than 0 and not greater than 6 wt%, optionally greater than 0 and not greater than 5.5 wt%, and further optionally 2 to 4 wt%, and / or The coverage of the third coating layer is, based on the weight of the core, greater than 0 and less than 6 wt%, optionally greater than 0 and less than 5.5 wt%, and further optionally greater than 0 and less than 2 wt%, for example 1%.
[0103] In the second positive electrode active material having a core-shell structure of the present application, the coating amount of the three coating layers is preferably within the above range, so that the core can be sufficiently coated, and at the same time, the gram capacity of the positive electrode active material is not sacrificed, and the dynamic performance and safety performance of the secondary battery are further improved.
[0104] For the first coating layer, by setting the coating amount within the above range, the following situation can be avoided: if the coating amount is too small, it means that the coating layer is too thin and may not be able to effectively inhibit the transition of transition metals; if the coating amount is too large, the coating layer is too thick and may not be able to effectively inhibit the transition of Li + This means that the transition between the .DELTA. and .DELTA. phases will be affected, which in turn will affect the rate performance of the material.
[0105] For the second coating layer, by setting the coating amount within the above range, the following situation can be avoided: if the coating amount is too large, it may affect the plateau voltage of the entire material, and if the coating amount is too small, it may not be possible to achieve a sufficient coating effect.
[0106] For the third coating layer, the carbon coating mainly plays the role of reinforcing the electron transmission between particles, but because the structure further contains a large amount of amorphous carbon, the density of carbon is relatively low, so if the coating amount is too large, it will affect the compaction density of the electrode plate.
[0107] In some embodiments, in the second positive electrode active material, the first coating layer has a thickness of 1 to 10 nm.
[0108] In some embodiments, in the second active cathode material, the thickness of the first coating layer can be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, or about 10 nm, or any range between any of the above numerical values.
[0109] In the present application, when the thickness range of the first coating layer is 1 to 10 nm, it is possible to avoid the adverse effect on the dynamic performance of the material that may occur when the first coating layer is too thick, and to avoid the problem of not being able to effectively inhibit the transition of transition metal ions when the first coating layer is too thin.
[0110] In some embodiments, in the second positive electrode active material, the second coating layer has a thickness of 2 to 15 nm, and optionally 2.5 to 7.5 nm.
[0111] In some embodiments, in the second active cathode material, the thickness of the second coating layer can be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, or any range between any of the preceding numerical values.
[0112] In the present application, when the thickness of the second coating layer is within the above range, the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so that the interfacial side reaction can be effectively reduced, thereby improving the high-temperature performance of the secondary battery.
[0113] In some embodiments, in the second positive electrode active material, the third coating layer has a thickness of 2 to 25 nm.
[0114] In some embodiments, in the second positive electrode active material, the thickness of the coating layer of the third layer can be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, about 16 nm, about 17 nm, about 18 nm, about 19 nm, about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm, or about 25 nm, or any range between any of the numerical values above.
[0115] In the present application, when the thickness range of the third coating layer is 2 to 25 nm, it can enhance the electrical conductivity performance of the material and improve the compaction density performance of the battery plate manufactured using the first positive electrode active material.
[0116] The thickness dimension test of the coating layer is mainly performed by FIB, and the specific method may include the following steps: randomly select a single particle from the second positive electrode active material powder to be measured, cut out a slice with a thickness of about 100 nm from the middle position or near the middle position of the selected particle, and perform a TEM test on the slice to measure the thickness of the coating layer, measuring 3 to 5 points and taking the average value.
[0117] In some embodiments, the manganese content in the second positive electrode active material is in the range of 10 wt % to 35 wt %, optionally in the range of 15 wt % to 30 wt %, and further optionally in the range of 17 wt % to 20 wt %, based on the weight of the second positive electrode active material.
[0118] In the present application, when manganese is contained only in the core of the second positive electrode active material, the manganese content may correspond to the content of the core.
[0119] In the second positive electrode active material having a core-shell structure of the present application, the manganese content within the above range can effectively avoid problems such as poor stability of material structure and reduced density that may occur when the manganese content is too high, thereby improving the performance of the secondary battery in terms of cycle, storage and compaction density, etc., and can avoid problems such as low voltage plateau that may occur when the manganese content is too low, thereby improving the energy density of the secondary battery.
[0120] In some embodiments, the second positive electrode active material has a phosphorus content in the range of 12 wt % to 25 wt %, and optionally in the range of 15 wt % to 20 wt %, based on the weight of the second positive electrode active material.
[0121] In the second positive electrode active material having a core-shell structure of the present application, the content of phosphorus within the above range can effectively avoid the following situation: if the content of phosphorus is too large, the covalent bond of PO is too strong, which may affect the conductivity of small polaritons, thereby affecting the conductivity of the material; if the content of phosphorus is too small, the stability of the core, the pyrophosphate in the first coating layer and / or the phosphate lattice structure in the second coating layer may be reduced, thereby affecting the stability of the entire material.
[0122] In some embodiments, in the second positive electrode active material, the weight ratio of elemental manganese to elemental phosphorus, based on the weight of the second positive electrode active material, ranges from 0.90 to 1.25, and optionally from 0.95 to 1.20.
[0123] In the second positive electrode active material having a core-shell structure of the present application, the weight ratio of manganese to phosphorus within the above range can effectively avoid the following situation: if the weight ratio is too large, it means that the amount of manganese element is too much, which increases the elution of manganese, affecting the stability and gram capacity of the second positive electrode active material, and further affecting the cycle performance and storage performance of the secondary battery; if the weight ratio is too small, it means that the amount of phosphorus element is too much, which is easy to form a heterophase, which reduces the discharge voltage plateau of the material, and thereby reduces the energy density of the secondary battery.
[0124] The manganese and phosphorus elements can be measured by the general technical means in the art. In particular, the manganese and phosphorus elements are measured by the following method: dissolving the material in dilute hydrochloric acid (concentration 10-30%), testing the content of each element in the solution using ICP, and measuring and converting the manganese element content to obtain the weight ratio.
[0125] In some embodiments, the lattice change rate of the second positive electrode active material before and after complete lithium release is 4% or less, optionally 3.8% or less, and further optionally 2.0 to 3.8%.
[0126] The lithium release process of lithium manganese phosphate (LiMnPO4) is a two-phase reaction. The interfacial stress between the two phases is determined by the magnitude of the lattice change rate before and after the lithium release. The smaller the lattice change rate and the smaller the interfacial stress, the greater the Li + Therefore, the decrease in the lattice change rate of the core is + It is advantageous to reinforce the transmission ability of the secondary battery, thereby improving the rate performance of the secondary battery. Since the second positive electrode active material having a core-shell structure of the present application can realize a lattice change rate of 4% or less before and after releasing lithium, the rate performance of the secondary battery can be improved by using the second positive electrode active material. The lattice change rate can be measured by a method known in the art, for example, X-ray diffraction spectrum (XRD).
[0127] In some embodiments, the second positive electrode active material has a Li / Mn antisite defect concentration of 4% or less, optionally 2.2% or less, and further optionally 1.5-2.2%.
[0128] The Li / Mn antisite defect in this application is Li + and Mn 2+ The position of the Li / Mn antisite defect is interchanged. 2+ Replaced by Li + Li + In the present application, the Li / Mn antisite defect concentration can be tested, for example, according to JIS K 0131-1996.
[0129] The second positive electrode active material having a core-shell structure of the present application can realize the above-mentioned relatively low Li / Mn antisite defect concentration. Although the mechanism has not yet been fully clarified, the inventors of the present application speculate that in the LiMnPO4 lattice, Li + and Mn 2+ The positions of Li are interchanged. + Since the transmission channel is one-dimensional, Mn 2+ Li + It is difficult to change channels, and Li + Therefore, the second positive electrode active material having a core-shell structure of the present application has a relatively low Li / Mn antisite defect concentration within the above range, and therefore Mn 2+ Li + This avoids impeding the transmission of the charge and improves the gram capacity and rate performance of the second positive electrode active material.
[0130] In some embodiments, the second positive electrode active material has a packed density at 3 T of 2.2 g / cm 3 or more, and optionally 2.2 g / cm 3 Above 2.8g / cm 3The higher the packed density, the greater the weight of active material per unit volume, so improving the packed density is advantageous for improving the volumetric energy density of the cell. The packed density can be measured according to GB / T 24533-2009.
[0131] In some embodiments, the surface oxygen valence of the second positive electrode active material is less than or equal to −1.90, and optionally between −1.90 and −1.98.
[0132] The stable valence of oxygen is originally -2, and the closer the valence is to -2, the stronger its ability to obtain electrons, i.e., the stronger its oxidizing property. In general, its surface valence is -1.7 or less. In the present application, by limiting the surface oxygen valence of the first positive electrode active material to the above range as described above, it is possible to reduce the interfacial side reaction between the second positive electrode active material and the electrolyte, thereby improving the performance of the cell in terms of cycle, high-temperature storage, gas generation, etc.
[0133] Surface oxygen valence may be measured by methods known in the art, for example, by electron energy loss spectroscopy (EELS).
[0134] In some embodiments, the average particle size range of the primary particles of the second positive electrode active material is 50-500 nm, and the volume median particle size Dv50 is within the range of 200-300 nm. Since the particles aggregate, the size of the secondary particles after aggregation may be 500-40000 nm. The size of the particles of the second positive electrode active material affects the processing of the material and the compaction density performance of the electrode plate. By selecting the average particle size of the primary particles within the above range, the following situations can be avoided: if the average particle size of the primary particles of the second positive electrode active material is too small, the particles will aggregate, making it difficult to disperse, and a relatively large amount of adhesive will be required, and the brittleness of the electrode plate may be relatively poor; if the average particle size of the primary particles of the second positive electrode active material is too large, the gap between the particles will be relatively large, which may reduce the compaction density.
[0135] The above method can effectively suppress the lattice change rate of lithium manganese phosphate and the Mn dissolution during lithium release, thereby improving the high-temperature cycle stability and high-temperature storage performance of the secondary battery.
[0136] In the present application, the median particle size Dv50 is the particle size corresponding to the cumulative volume distribution percentage of the material reaching 50%. In the present application, the median particle size Dv50 of the material can be measured by using a laser diffraction granulometry method, for example, referring to the standard GB / T 19077-2016, and using a laser granulometer (e.g. Malvern Master Size 3000).
[0137] Process control (e.g., thoroughly mixing and grinding various source materials) can ensure that each element is uniformly distributed in the lattice without aggregation. The main feature peak position in the XRD diagram of lithium manganese phosphate after doping with A and R elements is consistent with that of undoped LiMnPO4, indicating that no impurity phase is introduced in the doping process, so the improvement of core performance is mainly due to element doping, not due to heterophase. After producing the second positive electrode active material, the inventor of the present application cut out the middle region of the second positive electrode active material particle already produced by focused ion beam (abbreviated as FIB), and tested it by transmission electron microscope (abbreviated as TEM) and X-ray spectroscopy (abbreviated as EDS), and found that each element is uniformly distributed without aggregation.
[0138] In some embodiments, in the second positive electrode active material, A is one or more elements selected from Fe, Ti, V, Ni, Co, and Mg, and optionally one or more elements selected from Fe, V, Ni, Co, and Mg, and further optionally one or more elements selected from Fe, V, and Ni. Selecting a doping element within the above range is advantageous for enhancing the doping effect, and on the one hand, further reducing the lattice change rate, thereby suppressing the dissolution of manganese and reducing the consumption of the electrolyte and active lithium, and on the other hand, further reducing the oxygen activity of the surface, thereby reducing the interfacial side reaction between the first positive electrode active material and the electrolyte, thereby further improving the cycle performance and high-temperature storage performance of the secondary battery.
[0139] In some embodiments, in the second positive electrode active material, R is selected from one of the elements B, Si, N, and S, and optionally R is one or more elements selected from Si, N, and S, and further optionally Si. By selecting the doping element within the above range, the rate performance of the secondary battery can be further improved and the electrical conductivity can be improved, thereby enhancing the gram capacity, cycle performance, and high temperature performance of the secondary battery.
[0140] In some embodiments, in the core of the second positive electrode active material, x is any number within the range of −0.005 to 0.002, such as −0.004, −0.003, −0.002, −0.001, 0, 0.001, 0.002.
[0141] In some embodiments, in the core of the second active cathode material, y can be, for example, 0.001, 0.002, 0.3, 0.35, 0.4, 0.5.
[0142] In some embodiments, in the core of the second active cathode material, z can be, for example, 0.001, 0.002, 0.003, 0.005, 0.1.
[0143] In some embodiments, the first coating layer of the second active cathode material comprises crystalline Li pyrophosphate.a MP2O7 and M b (P2O7) c In the formula, M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, and Al, and is, for example, Fe.
[0144] In some embodiments, in the first coating layer of the second positive electrode active material, a is selected from the range of 1 to 2, for example, 2.
[0145] In some embodiments, b can be 1, 2, 3, or 4 in the first coating layer of the second active cathode material.
[0146] In some embodiments, c is selected from the range of 1-3 in the first coating layer of the second positive electrode active material.
[0147] In some embodiments, in the second coating layer of the second active cathode material, X is selected from two elements of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, e.g., Li and Fe, i.e., the crystalline phosphate XPO4 is crystalline LiFePO4.
[0148] [Method for producing positive electrode active material] One embodiment of the present application provides a method for producing a cathode active material, the method comprising: providing a first active cathode material and a second active cathode material; mixing a first positive electrode active material with a second positive electrode active material; The first positive electrode active material is the compound LiNi g Co d Mn e M' f O2, the second positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the core is a compound Li 1+x Mn 1-y A y P1-z R z O4, and the first coating layer is crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c and the second coating layer comprises a crystalline phosphate X n PO4, and the third coating layer comprises carbon, wherein g, d, e, f, x, y, z, a, b, c, n, A, R, M, X, and M' are defined as described in "[Positive Electrode Active Material]", Optionally, the first positive electrode active material further includes lithium carbonate and / or lithium hydroxide.
[0149] As a result, the present application uses a mixture of a first positive electrode active material and a second positive electrode active material to complement the advantages of the two materials, improve the cycle capacity retention rate of the secondary battery, extend the cycle life of the secondary battery, and enhance the safety of the secondary battery.
[0150] In some embodiments, the first active cathode material is made by the steps of: Step 1): React Ni salt, Co salt, Mn salt with an alkali in a solvent, perform solid-liquid separation, and collect the solid phase. Step 2): Mixing the solid phase material, the lithium source, and the source of element M, ball milling, sintering, and cooling to obtain a first positive electrode active material; Optionally, in step 2), the first positive electrode active material after cooling is crushed and sieved, or the first positive electrode active material after cooling is crushed, resintered, crushed and sieved.
[0151] In some embodiments, in step 1), the reaction is carried out under conditions of a pH value of 9-13, and optionally under conditions of a pH value of 9-12 or 10-13.
[0152] In some embodiments, in step 1), the reaction temperature is between 40°C and 80°C, for example 50°C, 55°C, 60°C.
[0153] In some embodiments, in step 1), the reaction time is 8 to 70 hours, for example, 20 hours, 55 hours, 60 hours, 65 hours.
[0154] In some embodiments, in step 1), the reaction is carried out under conditions of a rotation speed of 150 to 1000 r / min, for example, 300 r / min or 500 r / min.
[0155] In some embodiments, in step 1), the solid-liquid separation is filtration.
[0156] In some embodiments, prior to step 2), the solid phase is washed, dried, and optionally vacuum dried at 100° C.-140° C. for 12-48 h, such as at 120° C. for 24 h.
[0157] In some embodiments, in step 2), the rotation speed of the ball mill is 200-500 r / s, for example, 300 r / s, 500 r / s.
[0158] In some embodiments, in step 2), the ball milling time is 1-5 h, for example, 2, 3, 4 h.
[0159] In some embodiments, in step 2), sintering is performed in an air atmosphere, optionally at 0.1-0.4 MPa.
[0160] In some embodiments, in step 2), the sintering procedure is to increase the temperature to 750°C-950°C and hold for 12-20 hours for pre-sintering, with a heating rate of 1°C / min, and optionally decrease the temperature to 600°C at the same rate and hold for 8 hours for sintering, and after sintering, decrease the temperature to 300°C at a rate of 1°C / min.
[0161] In some embodiments, in step 2), the re-sintering procedure is to heat the material to 400°C at a rate of 20°C / min, hold the material at this temperature for 20 hours, and then cool the material to 300°C at a rate of 1°C / min after sintering.
[0162] In some embodiments, in step 2), the powder is pulverized using an airflow pulverizer, and optionally the rotation speed of the airflow pulverizer is 2500-3500 r / min, for example 3000 r / min, and optionally the air volume of the airflow pulverizer is 400-600 m 3 / h, e.g. 500m 3 / h.
[0163] In some embodiments, step 2) involves sieving through a 450-550 mesh (eg, 500 mesh) screen.
[0164] In some embodiments, a method for producing a second cathode active material includes the steps of: Providing a core material: the core chemical formula is Li 1+x Mn 1-y A y P 1-z R z O4, where x is any number within the range of -0.100 to 0.100, y is any number within the range of 0.001 to 0.600, z is any number within the range of 0.001 to 0.100, A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Fe, V, Ni and Co, R is one or more elements selected from B, Si, N and S, and optionally one or more elements selected from Si, N and S, Coating step: Li a MP2O7 and / or M b (P2O7) c and X n PO4 suspension is provided, and a core material is added to the suspension and mixed, and then sintered to obtain a first positive electrode active material, where a is greater than 0 and less than or equal to 2, b is selected from the range of 1 to 4, and c is selected from the range of 1 to 3, and the values of a, b and c are each a crystalline pyrophosphate Li a MP2O7 or M b (P2O7) cM is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and optionally one or more elements selected from Fe, Co, Ti and Al; X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and optionally one or more elements selected from Li, Fe, Ag and Al; Here, the first positive electrode active material has a core-shell structure, which includes a core, a first coating layer coating the core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, and the first coating layer is made of crystalline pyrophosphate Li a MP2O7 and / or M b (P2O7) c and the second coating layer comprises a crystalline phosphate X n The first coating layer is PO4 and the third coating layer is carbon.
[0165] In some embodiments, the step of providing the core material comprises the steps of: Step (1): Mixing a manganese source, a source of element A, and an acid to obtain a mixture; Step (2): Mix the mixture with a lithium source, a phosphorus source, a source of element R, and a selective solvent, and sinter under inert gas protection to obtain Li 1+x Mn 1-y A y P 1-z R z A core material containing O4 is obtained, where A, R, x, y and z are as defined above.
[0166] The manufacturing method of the present application is not particularly limited with respect to the origin of the material, and the origin of a certain element may include one or more of the element's simple substance, sulfate, halide, nitrate, organic acid salt, oxide, or hydroxide, provided that the origin can achieve the objective of the manufacturing method of the present application.
[0167] In some embodiments, in the step of providing a core material, the source of element A is one or more selected from an elemental salt, a carbonate, a sulfate, a chloride, a nitrate, an organic acid salt, an oxide, and a hydroxide of element A.
[0168] In some embodiments, in the step of providing a core material, the source of element R is one or more selected from inorganic acids, subacids, organic acids, sulfates, chlorides, nitrates, organic acid salts, oxides and hydroxides of element R.
[0169] In some embodiments, in the step of providing a core material, the manganese source may be any manganese-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the manganese source may be one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.
[0170] In some embodiments, in the step of providing the core material, the acid may be one or more selected from inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, silicic acid, metasilicic acid, and organic acids, for example oxalic acid.
[0171] In some embodiments, the acid is a dilute organic acid at a concentration of 60% by weight or less.
[0172] In some embodiments, in the step of providing the core material, the lithium source may be any lithium-containing material known in the art that can be used to prepare lithium manganese phosphate, for example, the lithium source may be one or more selected from lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.
[0173] In some embodiments, in the step of providing a core material, the phosphorus source may be any phosphorus-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the phosphorus source may be one or more selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.
[0174] In some embodiments, in the step of providing a core material, a manganese source, a source of element A, and an acid are reacted in a solvent to obtain an element A-doped manganese salt suspension, which is then filtered, dried, and sand-milled to obtain element A-doped manganese salt particles having a particle size of 50-200 nm.
[0175] In some embodiments, the step of providing a core material comprises drying the slurry in step (2) to obtain a powder, and sintering the powder to obtain a core doped with element A and element R.
[0176] In some embodiments, step (1) comprises mixing at a temperature between 20 and 120° C., optionally between 40 and 120° C.; and / or The stirring in step (1) is carried out at 400-700 rpm for 1-9 h, optionally for 3-7 h; Alternatively, the reaction temperature in step (1) may be about 30°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C or about 120°C, and the stirring in step (1) may be performed for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours or about 9 hours, and optionally, the reaction temperature and stirring time in step (1) may be within any range of any of the above numerical values.
[0177] In some embodiments, step (2) is performed at a temperature of 20 to 120°C, optionally 40 to 120°C, for 1 to 12 hours; optionally, the reaction temperature in step (2) may be about 30°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, or about 120°C; the mixing in step (2) is performed for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, about 10 hours, about 11 hours, or about 12 hours; optionally, the reaction temperature and mixing time in step (2) may be within any range of any of the above numerical values.
[0178] When the temperature and time during the core particle production process are within the above ranges, the lattice defects in the produced core and the second positive electrode active material produced therefrom are relatively few, which is advantageous in suppressing the dissolution of manganese and reducing the interfacial side reactions between the positive electrode active material and the electrolyte, thereby improving the cycle performance and safety performance of the secondary battery.
[0179] In some embodiments, in the process of preparing the dilute acid manganese particles doped with A and R elements in the step of providing a core material, the solution pH is controlled to 3.5-6, optionally the solution pH is controlled to 4-6, and further optionally the solution pH is controlled to 4-5. It should be noted that in the present application, the pH of the mixture obtained may be adjusted by a method commonly used in the art, such as by adding an acid or alkali.
[0180] In some embodiments, in step (2), the molar ratio of the manganese salt particles to the lithium source to the phosphorus source is 1:0.5-2.1:0.5-2.1, and optionally, the molar ratio of the manganese salt particles doped with element A to the lithium source to the phosphorus source is about 1:1:1.
[0181] In some embodiments, in the step of providing a core material, the sintering conditions in the process of preparing lithium manganese phosphate doped with A and R elements are sintering in an inert gas or a mixed atmosphere of inert gas and hydrogen gas at 600-950°C for 4-10 hours, optionally sintering at about 650°C, about 700°C, about 750°C, about 800°C, about 850°C or about 900°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours or about 10 hours, optionally the sintering temperature and sintering time may be within any range of any of the above values. In the process of preparing lithium manganese phosphate doped with A and R elements, if the sintering temperature is too low and the sintering time is too short, the crystallinity of the core of the material will be relatively low, which will affect the overall performance; if the sintering temperature is too high, the core of the material will be prone to heterophase, which will affect the overall performance; if the sintering time is too long, the length of the core particles of the material will be relatively large, which will affect the gram capacity, compaction density and rate performance, etc.
[0182] In some embodiments, in the step of providing the core material, the protective atmosphere is a mixture of 70-90% by volume of nitrogen gas and 10-30% by volume of hydrogen gas.
[0183] In some embodiments, the coating step includes: First coating step: dissolving a source of element M, a phosphorus source and an acid and optionally a lithium source in a solvent to obtain a suspension of a first coating layer, thoroughly mixing the core obtained in the core step with the suspension of the first coating layer obtained in the first coating step, drying and sintering to obtain a material coated with a first coating layer; Second coating step: dissolving a source of element X, a phosphorus source and an acid in a solvent to obtain a suspension of a second coating layer; thoroughly mixing the material coated with the first coating layer obtained in the first coating step and the suspension of the second coating layer obtained in the second coating step, drying and sintering to obtain a material coated with two coating layers; Third coating step: dissolve the carbon source in a solvent and dissolve it sufficiently to obtain a third coating layer solution, and then put the material coated with two coating layers obtained in the second coating step into the third coating layer solution, mix uniformly, dry, and sinter to obtain a material coated with three coating layers, i.e., a second positive electrode active material.
[0184] In some embodiments, in the coating step, the source of element M is one or more selected from the elemental salts, carbonates, sulfates, chlorides, nitrates, organic acid salts, oxides, and hydroxides of one or more of the following elements: Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, or Al.
[0185] In some embodiments, the source of element M' is one or more selected from the group consisting of an elemental salt, a carbonate, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydroxide of element M'.
[0186] In some embodiments, in the coating step, the source of element X is one or more selected from the elemental salts, carbonates, sulfates, chlorides, nitrates, organic acid salts, oxides, and hydroxides of one or more of the following elements: Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, or Al.
[0187] The amount of each of the sources of elements A, R, M, and X added depends on the target doping amount, and the ratio of the amount of the lithium source, the manganese source, and the phosphorus source used is in accordance with the stoichiometric ratio.
[0188] By way of example, the carbon source is one or more selected from starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, citric acid.
[0189] In some embodiments, in the first coating step, the solution containing the source of element M, the phosphorus source, the acid, and optionally the lithium source is controlled to a pH of 3.5-6.5 and stirred to react for 1-5 h, and then the solution is heated to 50-120° C. and maintained at this temperature for 2-10 h, and / or sintering is performed at 650-800° C. for 2-6 hours.
[0190] In some embodiments, the reaction in the first coating step is allowed to proceed for a sufficient period of time. Optionally, the reaction in the first coating step is allowed to proceed for about 1.5 hours, about 2 hours, about 3 hours, about 4 hours, about 4.5 hours, or about 5 hours. Optionally, the reaction time in the first coating step can be within any range of any of the values recited above.
[0191] In some embodiments, in the first coating step, the solution pH is controlled between 4 and 6. Optionally, in the first coating step, the solution is heated to about 55° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C. and maintained at this temperature for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours, and optionally, in the first coating step, the elevated temperature and the maintenance time can be within any range of any of the above numerical values.
[0192] In some embodiments, in the first coating step, sintering may be at about 650° C., about 700° C., about 750° C., or about 800° C. for about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours, optionally with the sintering temperature and sintering time within any range of any of the above numerical values.
[0193] In the first coating step, by controlling the sintering temperature and time within the above ranges, the following situations can be avoided: if the sintering temperature and sintering time in the first coating step are too low and too short, the crystallinity of the first coating layer will be low and the amount of amorphous material will be relatively large, thus reducing the effect of inhibiting the dissolution of metals, thereby affecting the cycle performance and high-temperature storage performance of the secondary battery; if the sintering temperature is too high, a hetero phase will be generated in the first coating layer, which will also affect the effect of inhibiting the dissolution of metals, thereby affecting the cycle performance and high-temperature storage performance of the secondary battery; if the sintering time is too long, the thickness of the first coating layer will increase, and the Li + This affects the transition of the material and thereby the gram capacity and rate performance of the material.
[0194] In some embodiments, in the second coating step, the source of element X, the phosphorus source and the acid are dissolved in a solvent, then stirred and reacted for 1-10 h, and the solution is heated to 60-150° C. and maintained at this temperature for 2-10 h, and / or sintering is performed at 500-700° C. for 6-10 h.
[0195] Optionally, in the second coating step, the reaction is allowed to proceed for a sufficient period of time. Optionally, in the second coating step, the reaction is allowed to proceed for about 1.5 hours, about 2 hours, about 3 hours, about 4 hours, about 4.5 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours. Optionally, in the second coating step, the reaction time of the reaction can be within any range of any of the above numerical values.
[0196] Optionally, in the second coating step, the solution is heated to about 65°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C or about 150°C and maintained at this temperature for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours or about 10 hours, and optionally, in the second coating step, the elevated temperature and maintenance time can be within any range of any of the above numerical values.
[0197] In the step of providing a core material and the first and second coating steps, before sintering, i.e., in the production of the core material where chemical reactions occur (steps (1)-(2)) and in the production of the suspension of the first coating layer and the suspension of the second coating layer, by selecting an appropriate reaction temperature and reaction time as described above, the following situations can be avoided: if the reaction temperature is too low, the reaction cannot occur or the reaction rate is slow; if the temperature is too high, the product will be decomposed or a heterophase will be formed; if the reaction time is too long, the particle size of the product will be relatively large, which may increase the time and difficulty of subsequent processes; if the reaction time is too short, the reaction will be incomplete and the product obtained will be relatively small.
[0198] Optionally, in the second coating step, sintering may be performed at about 550°C, about 600°C, or about 700°C for about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours, and optionally the sintering temperature and sintering time may be within any range of any of the above numerical values.
[0199] In the second coating step, by controlling the sintering temperature and time within the above ranges, the following situations can be avoided: if the sintering temperature and sintering time in the second coating step are too low and too short, the second coating layer will have low crystallinity and relatively high amorphous content, which will reduce the performance of reducing the surface reaction activity of the material, thereby affecting the cycle and high-temperature storage performance of the secondary battery; if the sintering temperature is too high, a heterophase will be generated in the second coating layer, which will also affect the effect of reducing the surface reaction activity of the material, thereby affecting the cycle and high-temperature storage performance of the secondary battery; if the sintering time is too long, the thickness of the second coating layer will increase, which will affect the voltage plateau of the material, thereby resulting in a decrease in the energy density of the material, etc.
[0200] In some embodiments, the sintering in the third coating step is performed for 6 to 10 hours at 700-800° C. Alternatively, the sintering in the third coating step may be performed at about 700° C., about 750° C., or about 800° C. for about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours, and optionally the sintering temperature and sintering time may be within any range of any of the above numerical values.
[0201] In the third coating step, the sintering temperature and time can be controlled within the above ranges to avoid the following situation: if the sintering temperature in the third coating step is too low, the graphitization degree of the third coating layer will be reduced, affecting its electrical conductivity, and thus affecting the gram capacity of the material; if the sintering temperature is too high, the graphitization degree of the third coating layer will be too high, resulting in the Li + If the sintering time is too short, the coating layer will be too thin, which will affect its conductivity, thereby affecting the gram capacity of the material; if the sintering time is too long, the coating layer will be too thick, which will affect the compaction density of the material.
[0202] In the above first coating step, second coating step, and third coating step, drying is performed at a drying temperature of 100°C to 200°C, optionally 110°C to 190°C, further optionally 120°C to 180°C, further optionally 120°C to 170°C, and most optionally 120°C to 160°C, and the drying time is 3 to 9 hours, optionally 4 to 8 hours, further optionally 5 to 7 hours, and most optionally about 6 hours.
[0203] [Positive electrode plate] The positive electrode plate generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the above-mentioned positive electrode active material or the positive electrode active material produced by the above-mentioned method.
[0204] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and a positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0205] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0206] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0207] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0208] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.
[0209] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0210] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.
[0211] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0212] In some embodiments, the negative electrode active material may be a negative electrode active material used in batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicone alone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as battery negative electrode active materials may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0213] In some embodiments, the negative electrode membrane layer further optionally includes an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS), for example.
[0214] In some embodiments, the negative electrode film layer further optionally includes a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0215] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0216] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.
[0217] [Electrolytes] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.
[0218] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.
[0219] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0220] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0221] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.
[0222] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.
[0223] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, and there is no particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and there is no particular limitation.
[0224] In some embodiments, the positive and negative plates and the separator may be formed into an electrode assembly by a winding or lamination process.
[0225] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.
[0226] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0227] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 2 shows a secondary battery 5 having a rectangular structure as an example.
[0228] In some embodiments, referring to FIG. 3, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is permeated into the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and those skilled in the art can select it according to the actual needs.
[0229] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.
[0230] Fig. 4 shows an example of a battery module 4. Referring to Fig. 4, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.
[0231] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.
[0232] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.
[0233] 5 and 6 show an example of a battery pack 1. Referring to Fig. 5 and Fig. 6, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box may include an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0234] The present application further provides a power consuming device, which includes at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0235] As the power consuming device, a secondary battery, a battery module, or a battery pack can be selected according to the usage demand.
[0236] 7 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the secondary battery of the power consumption device.
[0237] [Example] The following describes the manufacturing examples of the present application. The manufacturing examples described below are illustrative and are used only to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the manufacturing examples, they are carried out according to the techniques or conditions described in the literature in the field or according to the product specifications. If no manufacturer is specified, the reagents or equipment used are all ordinary products available from the market.
[0238] Preparation of the first positive electrode active material Manufacturing example A3: LiNi 0.55 Co 0.113 Mn 0.277 Al 0.04 Mg 0.02 O2 (single crystal-like) (1) Prepare a mixed solution of NiSO4, CoSO4 and MnSO4 in a molar ratio of 0.55:0.113:0.277 by adding water, where the concentration of NiSO4 in the mixed solution is 2 mol / L, and prepare a 5 mol / L NaOH solution. (2) 50L of the mixed solution is introduced into the reaction tank, and 50L of NaOH solution and an appropriate amount of 0.5mol / L of ammonia aqueous solution are further introduced into the reaction tank. The pH value in the reaction tank is 9.0-12.0, the reaction temperature is 40℃-80℃, and the reaction is carried out under stirring conditions for 60 hours. The stirring rotation speed is 300-1000r / min. After completion, the precipitate is filtered and washed, and the washed precipitate is vacuum dried at 120℃ for 24 hours to obtain a precursor. (3) Li2CO3, precursor, Al2O3 and MgO are mixed, where the molar ratio of Li2CO3 (in terms of the molar amount of Li element), precursor (in terms of the total molar amount of the three elements of Ni, Co and Mn in the mixed solution), Al2O3 (in terms of the molar amount of Al element) and MgO is 1.05:0.94:0.04:0.02. After mixing, it is placed in a ball mill tank and ball milled at a rotation speed of 300 r / s for 2 hours, and then placed in a van furnace and pre-sintered in an air atmosphere of 0.2 MPa by heating to 950 °C and keeping the temperature for 12 hours. The heating rate is 1 °C / min, and then the temperature is reduced to 600 °C at a rate of 1 °C / min and kept at that temperature for 8 hours. After sintering, the temperature is reduced to 300 °C at a rate of 1 °C / min, and then naturally cooled to room temperature. Then, it is passed through an air flow mill and sintered at a rotation speed of 3000 r / min for 500 m. 3 / h, crushed for 0.5 h, and sieved through a 500 mesh screen to obtain a first positive electrode active material.
[0239] Manufacturing example A16: LiNi 0.83 Co 0.114 Mn 0.006 Al 0.04 Mg 0.01 O2 (polycrystalline) (1) Prepare a mixed solution of NiSO4, CoSO4 and MnSO4 in a molar ratio of 0.83:0.114:0.006 by adding water, where the concentration of NiSO4 in the mixed solution is 2 mol / L, and prepare a 6 mol / L NaOH solution. (2) 50L of the mixed solution is introduced into the reaction tank, and 50L of NaOH solution and an appropriate amount of 0.5mol / L of ammonia aqueous solution are further introduced into the reaction tank. The pH value in the reaction tank is 10-13, the reaction temperature is 40℃-80℃, and the reaction is carried out under stirring conditions for 8-20 hours. The stirring rotation speed is 150-300r / min. After completion, the precipitate is filtered and washed, and the washed precipitate is vacuum dried at 120℃ for 24 hours to obtain the precursor. (3) LiOH, precursor, Al2O3 and MgO were mixed, where the molar ratio of LiOH, precursor (converted into the total molar amount of the three elements Ni, Co and Mn in the mixed solution), Al2O3 (converted into the molar amount of Al element) and MgO was 1.05:0.95:0.04:0.01. After mixing, the mixture was placed in a ball mill tank and ball milled at a rotation speed of 500 r / s for 2 hours, and then placed in a van furnace, heated to 750°C in an air atmosphere of 0.2 MPa and kept at that temperature for 20 hours. Pre-sintering is performed, the temperature is increased at a rate of 20°C / min, and after sintering, the temperature is decreased to 300°C at a rate of 1°C / min, and then naturally cooled to room temperature, and crushed at a rotation speed of 2000r / min for 5 hours. The mixture is then heated to 400°C at a rate of 20°C / min and kept at that temperature for 20 hours before sintering. After sintering, the temperature is decreased to 300°C at a rate of 1°C / min, and then naturally cooled to room temperature, and then passed through an airflow crusher at a rotation speed of 3000r / min and crushed for 500m. 3 / h, crushed for 0.5 h, and sieved through a 400 mesh screen to obtain a first positive electrode active material.
[0240] Manufacturing Examples A1, A2, A4 to A15, A17 to A22 and Comparative Manufacturing Example A1 The first positive electrode active materials of Preparation Examples A1, A2, A4 to A11, A22 and Comparative Preparation Example A1 were prepared in a manner similar to Preparation Example A3. The differences in the preparation are shown in Table 1, and the rest are the same as Preparation Example A3. Manufacturing Examples A12 to A15 and A17 to A21 were manufactured in a manner similar to Manufacturing Example A16. The differences in the manufacturing process are shown in Table 1, and the rest are the same as Manufacturing Example A16.
[0241] JPEG2025503050000002.jpg250147 JPEG2025503050000003.jpg250166 JPEG2025503050000004.jpg250152
[0242] Preparation of second positive electrode active material Manufacturing example B1 Step S1: Preparation of manganese oxalate co-doped with Fe, Co, V and S 689.6g of manganese carbonate, 455.27g of ferrous carbonate, 4.65g of cobalt sulfate, and 4.87g of vanadium dichloride were mixed thoroughly in a blender for 6 hours. The mixture was then transferred to a reaction vessel, and 5L of deionized water and 1260.6g of oxalic acid dihydrate were added, heated to 80°C, and thoroughly stirred at a rotation speed of 500 rpm for 6 hours until no bubbles were generated and the reaction was completed, and a manganese oxalate suspension co-doped with Fe, Co, and V was obtained. The suspension was then filtered, dried at 120°C, and further crushed with sand to obtain manganese oxalate particles with a particle size of 100 nm.
[0243] Step S2: Core Li 0.997 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.997 S 0.003 O4 Production (1) 1793.1g of manganese oxalate, 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate and 4.9g of dilute sulfuric acid were added to 20L of deionized water, thoroughly stirred, and homogeneously mixed at 80℃ for 10h to obtain a slurry. The slurry was transferred to a spray drying machine for spray drying granulation, and dried at a temperature of 250℃ to obtain a powder. The powder was sintered in a roller hearth kiln at 700℃ for 4h in a protective atmosphere (90% nitrogen gas and 10% hydrogen gas) to obtain a core material. The element content detection was performed on the core material using inductively coupled plasma emission spectroscopy (ICP), and the obtained core chemical formula is as shown above.
[0244] Step S3: Preparation of the suspension of the first coating layer Preparation of LiFeP0 solution: 7.4g lithium carbonate, 11.6g ferrous carbonate, 23.0g ammonium dihydrogen phosphate and 12.6g oxalic acid dihydrate were dissolved in 500mL deionized water, the pH was controlled at 5, and the solution was stirred and reacted at room temperature for 2h to obtain a solution, which was then heated to 80°C and maintained at this temperature for 4h to obtain a suspension of the first coating layer.
[0245] Step S4: Coating the first coating layer 1571.9 g of the doped lithium manganese phosphate core material obtained in step S2 was added to the suspension of the first coating layer obtained in step S3 (the coating material content is 15.7 g), mixed thoroughly for 6 hours, and after uniform mixing, transferred to an oven at 120°C for drying for 6 hours, and then sintered at 650°C for 6 hours to obtain a pyrophosphate-coated material.
[0246] Step S5: Preparation of the suspension for the second coating layer 3.7 g of lithium carbonate, 11.6 g of ferrous carbonate, 11.5 g of ammonium dihydrogen phosphate and 12.6 g of oxalic acid dihydrate were dissolved in 1500 mL of deionized water and reacted with stirring for 6 hours to obtain a solution, which was then heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension of the second coating layer.
[0247] Step S6: Coating the second coating layer 1586.8 g of the pyrophosphate-coated material obtained in step S4 was added to the suspension of the second coating layer obtained in step S5 (the coating material content was 47.1 g), mixed thoroughly for 6 h, and then transferred to a 120°C oven for drying for 6 h after uniform mixing, and then sintered at 700°C for 8 h to obtain a two-layer coated material.
[0248] Step S7: Preparation of the aqueous solution of the third coating layer 37.3 g of sucrose was dissolved in 500 g of deionized water and thoroughly dissolved by stirring to obtain an aqueous sucrose solution.
[0249] Step S8: Coating the third coating layer 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and mixed together by stirring for 6 hours. After uniform mixing, the mixture was transferred to an oven at 150°C, dried for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.
[0250] Manufacturing Examples B2 to B52 and Comparative Manufacturing Examples B1 to B17 The positive electrode active materials of Preparation Examples B2 to B52 and Comparative Preparation Examples B1 to B17 were produced in a manner similar to that of Preparation Example B1. See Tables 2 to 7 for differences in the production of the positive electrode active materials.
[0251] Here, Comparative Production Examples B1 to B2, B4 to B10 and B12 do not have a first layer, so there are no steps S3 to S4, and Comparative Production Examples B1 to B11 do not have a second layer, so there are no steps S5 to S6.
[0252] JPEG2025503050000005.jpg250153 JPEG2025503050000006.jpg250162 JPEG2025503050000007.jpg250148JPEG2025503050000008.jpg25075
[0253] JPEG2025503050000009.jpg91169
[0254] JPEG2025503050000010.jpg225158 JPEG2025503050000011.jpg22535
[0255] JPEG2025503050000012.jpg88169
[0256] JPEG2025503050000013.jpg250157JPEG2025503050000014.jpg25045
[0257] JPEG2025503050000015.jpg250165 JPEG2025503050000016.jpg250122
[0258] Manufacturing example B30~B42 The positive electrode active materials of Preparation Examples B30 to B42 were produced in a manner similar to that of Preparation Example B1. See Tables 8 to 9 for differences in the production of the positive electrode active materials.
[0259] JPEG2025503050000017.jpg155169
[0260] JPEG2025503050000018.jpg138169
[0261] Manufacturing of mixed positive electrode active material Examples 1 to 49 and Comparative Example 1 The first positive electrode active material and the second positive electrode active material were mixed by stirring in a stirring tank, the mass of the first positive electrode active material was m1, the mass of the second positive electrode active material was m2, and the mass of the mixed positive electrode active material was m1+m2.
[0262] The parameters for each of the examples and comparative examples are as shown in Table 10.
[0263] JPEG2025503050000019.jpg250130
[0264] Full battery production The positive electrode active material, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as an adhesive were mixed uniformly in a weight ratio of 92:2.5:5.5 in an N-methylpyrrolidone solvent system, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode plate. The coating amount was 0.4 g / cm. 2 and the compaction density is 2.4g / cm 3 It is.
[0265] The negative electrode active materials, artificial graphite, hard carbon, conductive agent acetylene black, adhesive styrene butadiene rubber (SBR), and thickener sodium carboxymethylcellulose (CMC), were mixed uniformly in deionized water in a weight ratio of 90:5:2:2:1, and then coated on copper foil, dried, and cold pressed to obtain a negative electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 1.7 g / cm 3 It is.
[0266] A polyethylene (PE) porous polymer film was used as a separator, and a positive electrode plate, a separator, and a negative electrode plate were stacked in order so that the separator was located in the center of the positive and negative electrodes to play the role of isolation, and then rolled up to obtain a bare cell. The bare cell was placed in an exterior body, and the same electrolyte as that used to manufacture the button cell was injected and packaged to obtain a full battery (hereinafter also referred to as a "full cell").
[0267] Button battery manufacturing The positive electrode active material, polyvinylidene fluoride (PVDF), and acetylene black were added to N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and the mixture was stirred in a drying chamber to prepare a slurry. The slurry was coated on an aluminum foil, dried, and cold pressed to prepare a positive electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 2.0 g / cm 3 It is.
[0268] A lithium sheet was used as the negative electrode, and 1 mol / L LiPF6 was dissolved in ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1 as the electrolyte. Together with the positive electrode plate produced above, this was assembled into a button cell box as a button battery (hereinafter also referred to as a "button cell").
[0269] The positive electrode active material may be a first positive electrode active material, a second positive electrode active material, or a mixed positive electrode active material.
[0270] Material Performance Testing 1. Measurement of the chemical formula of the positive electrode active material The internal microstructure and surface structure of the positive electrode active material were characterized with high spatial resolution using a spherical aberrometer (ACSTEM), and combined with three-dimensional reconstruction technology to obtain the core chemical formula of the positive electrode active material and the composition of the three coating layers.
[0271] 2. Lattice change rate measurement method In a constant temperature environment of 25°C, the positive electrode active material sample was placed in an XRD (model number is Bruker D8 Discover), and the sample was tested at 1° / min. The test data was analyzed and sorted, and the lattice constants a0, b0, c0 and v0 (a0, b0 and c0 represent the length of each side of the unit lattice, and v0 represents the volume of the unit lattice, which can be obtained directly from the XRD finishing result) were calculated by referring to the specification PDF card.
[0272] The positive electrode active material was prepared as a button cell according to the above "Preparation of Button Batteries", and the button cell was charged at a low rate of 0.05C until the current decreased to 0.01C. The positive electrode plate in the button cell was then taken out and placed in DMC for 8 hours for immersion. It was then dried, the powder was scraped off, and particles with a particle size of less than 500 nm were selected. The lattice constant v1 was calculated in the same manner as the fresh test sample above, and (v0-v1) / v0×100% was shown in the table as the lattice change rate before and after the lithium was completely released.
[0273] 3.Measuring method for Li / Mn antisite defect concentration The XRD results tested using the "Lattice Change Rate Measurement Method" were compared with the PDF (Powder Diffraction File) card of a standard crystal to obtain the Li / Mn antisite defect concentration. Specifically, the XRD results tested using the "Lattice Change Rate Measurement Method" were introduced into the General Structure Analysis System (GSAS) software to automatically obtain the refinement results, which included the occupancy status of different atoms, and the Li / Mn antisite defect concentration was obtained by reading the refinement results.
[0274] 4. Surface oxygen valence measurement method 5 g of the positive electrode active material sample was taken and fabricated into a button cell according to the above "Fabrication of Button Batteries". The button cell was charged at a low rate of 0.05 C until the current decreased to 0.01 C. The positive electrode plate in the button cell was then taken out and placed in DMC for 8 hours. It was then dried, the powder was scraped off, and particles with a particle size smaller than 500 nm were selected. The particles obtained were measured by electron energy loss spectroscopy (EELS, the model number of the equipment used was Talos F200S) to obtain the energy loss near edge structure (ELNES), which reflected the state density and energy level distribution of the elements. From the state density and energy level distribution, the valence of the surface oxygen after charging was estimated by integrating the valence band state density data and calculating the number of occupied electrons.
[0275] 5.Method of measuring consolidated density 5 g of the positive electrode active material powder was placed in a compaction mold (CARVER mold, model number 13 mm, USA), and the mold was placed on a compaction density meter. A pressure of 3 T was applied, and the powder thickness at pressure (thickness after decompression) was read on the instrument, and the compaction density was calculated from ρ = m / v.
[0276] 6. Method for measuring the amount of Mn (and Fe doped into Mn sites) dissolved after cycling The positive electrode active material sample was fabricated as a full battery according to "Fabrication of a Full Battery" above.
[0277] The full battery, which had been cycled at 45°C until the capacity had decayed to 80%, was discharged at a rate of 0.1 C to a cut-off voltage of 2.0 V. The battery was then disassembled, the negative electrode plate was removed, and 30 unit area (1540.25 mm2) pieces were placed on the negative electrode plate. 2 ) wafers were randomly taken and tested for inductively coupled plasma emission spectrum (ICP) using an Agilent ICP-OES730. Based on the ICP results, the amount of Fe (if Fe is doped on the Mn site of the positive electrode active material) and Mn were calculated, and the amount of Mn (and Fe doped on the Mn site) dissolved after cycling was calculated accordingly. The test standard complies with EPA-6010D-2014.
[0278] 7.Measuring the initial gram capacity of a button battery The button battery was charged at 0.1C from 2.5 to 4.3V up to 4.3V, then charged at a constant voltage of 4.3V until the current was 0.05mA or less, left to stand for 5min, and discharged at 0.1C down to 2.0V. The discharge capacity at this time was taken as the initial capacity and designated as D0.
[0279] 8.3C constant current charging ratio measurement method In a constant temperature environment of 25°C, a fresh full battery was left standing for 5 min, discharged at 1 / 3C to 2.5V. Left standing for 5 min, charged at 1 / 3C to 4.3V, and then charged at a constant voltage of 4.3V until the current was 0.05mA or less. Left standing for 5 min, the charge capacity at this time was recorded as C0. Discharged at 1 / 3C to 2.5V, left standing for 5 min, charged at 3C to 4.3V, left standing for 5 min, and the charge capacity at this time was recorded as C1. The constant current charging ratio at 3C is C1 / C0 x 100%.
[0280] The higher the charging constant current ratio at 3C, the better the rate performance of the battery.
[0281] 9. Cycle performance test of full battery at 45℃ In a constant temperature environment of 45°C, the full battery was charged at 1C from 2.5 to 4.3V to 4.3V, and then constant voltage charged at 4.3V until the current was 0.05mA or less. It was left to stand for 5min, and then discharged at 1C to 2.5V, and the discharge capacity at this time was recorded as D0. The above charge-discharge cycle was repeated until the discharge capacity decreased to 80% of D0. The number of cycles the battery had gone through was recorded.
[0282] 10. Full battery expansion test at 60℃ The full battery was stored at 60°C with a state of charge (SOC) of 100%. Before, during and after storage, the open circuit voltage (OCV) and internal resistance (IMP) of the cell were measured to monitor the SOC, and the cell volume was also measured. Here, after every 48 hours of storage, the full battery was taken out and left to stand for 1 hour before testing the open circuit voltage (OCV) and internal resistance (IMP). After cooling to room temperature, the cell volume was measured using the drainage method. In the drainage method, the gravity F1 of the cell was measured independently using a balance that automatically converts units using the dial data, and the cell was then completely immersed in deionized water (density 1 g / cm). 3 The cell is then placed in a container (known as a container for storing liquid) and the gravity F2 of the cell is measured. The buoyancy force F 浮 is F1-F2, and Archimedes principle F 浮 = ρ × g × V 排 Based on this, the cell volume V = (F1 - F2) / (ρ × g) was calculated.
[0283] From the results of the OCV and IMP tests, the battery of the embodiment always maintained an SOC of 99% or more until the end of storage in this experimental process.
[0284] After storage for 30 days, the cell volume was measured, and the increase rate of the cell volume after storage relative to the cell volume before storage was calculated.
[0285] The remaining capacity of the cell was also measured. A full battery was charged at 1C from 2.5 to 4.3V up to 4.3V, and then charged at a constant voltage of 4.3V until the current was 0.05mA or less. The battery was left to stand for 5min, and the charge capacity at this time was recorded as the remaining capacity of the cell.
[0286] 11. Specific surface area (BET) measurement method In accordance with GB / T 19587-2004, the specific surface area test was performed on the positive electrode active material using a specific surface area and porosity analyzer TRISTAR II 3020 (Micromeritics, USA). Before the test, the positive electrode active material was placed in a vacuum oven and dried at 200°C for ≥2h, with the sample weight >20g.
[0287] 12. Particle size Dv50 test The particle size Dv50 of the positive electrode active material was measured using a Mastersizer 3000 laser diffraction particle size analyzer (Malvern Panalytical) with reference to GB / T19077-2016, where deionized water was used as the solvent and the positive electrode active material was ultrasonicated for 5 min before the test.
[0288] 13. ICP Test (Inductively Coupled Plasma Atomic Emission Spectroscopy) Based on EPA 6010D-2014, the element content test was performed using an iCAP 7400 inductively coupled plasma optical emission spectrometer, and aqua regia was selected as the solvent. Formula for calculating powder element content: Element content (mass%) = 100% x element mass / sample mass. Formula for calculating the content of electrode plate elements: Element content (mass%) = 100% × element mass / (sample mass-current collector mass).
[0289] 14. Li2CO3 and LiOH content test (free lithium potential titration test) According to GB / T 9736-2008, the test is carried out using a 905 potentiometer, and after sampling, the aluminum plastic film bag is immediately vacuum sealed, and the minimum sample amount for one test is ≧30g.
[0290] 15.Crystal type test Unless otherwise specified, in this application, the terms "single crystal / single crystal-like particles", "quasi-single crystal particles", "single crystal particles", "single crystal material particles" and similar expressions basically have the same meaning and refer to single particles (i.e., primary particles) and / or agglomerated particles, among which agglomerated particles are particles formed by agglomeration of 100 or less (particularly about 5 to 50) primary particles having an average particle size in the range of 50 nm to 10,000 nm.
[0291] Unless otherwise specified, in this application, the terms "secondary particles" and "polycrystalline material particles" have generally similar meanings and refer to particles formed by agglomeration of more than 100 primary particles having an average particle size in the range of 50-800 nm.
[0292] The positive electrode active material was examined using a scanning electron microscope, the sample and magnification were adjusted so that there were more than 10 aggregate particles in the field of view, the number of primary particles constituting each aggregate particle was counted, and the longitudinal size of the primary particles was measured on a scale to determine the particle size, the particle sizes of the primary particles in each aggregate particle were sorted in ascending order, the data with the largest particle size being 1 / 10 and the data with the smallest particle size being 1 / 10 were removed, and the average of the remaining particle size data was taken to determine the average particle size of the primary particles in the aggregate particles. If the number and average particle size of primary particles in 50% or more (including 50%) of the aggregate particles met the above definition of "polycrystalline material particles," the positive electrode active material was determined to be a polycrystalline material, and if not, it was determined to be a single crystal or single crystal-like material.
[0293] 16. Hot Box Safety Test The test was carried out based on the "heating" chapter of the safety test in GB 38031-2020, and the upper limit was explored. The optimized test conditions are as follows:
[0294] (1) Preparation: Test conditions: Prepare an explosion-proof oven that can heat the wiring connection port. The test cell is a fresh bare cell (cycle count ≦ 10 times). Temperature-sensing wires are attached to the periphery of the cell and the poles, etc., for temperature monitoring, and a temperature recording device is installed. Cell treatment before testing: Constant current constant voltage charging was performed at a rate current of 0.33C to fully charge the cell to the nominal voltage (for example, in the present invention, the voltage is 4.3V).
[0295] (2) Test process: The sample was placed in a high-temperature bath, and the bath was heated from room temperature to 100°C at 5°C / min, maintained at that temperature for 2 hours, and then further heated at 5°C / min, maintaining each 5°C interval for 30 minutes, until the cell went out of control (runaway standard: voltage drop within 1 minute ≧ 50%, cell temperature rise within 1 minute ≧ 50%) or until it reached 200°C, at which point heating was stopped.
[0296] (3) Data processing: Based on the above conditions, the failure point was found, and the corresponding insulation temperature and insulation time were obtained, time@temperature, e.g. 21min@150℃.
[0297] (4) Results benchmark: Samples that last longer during testing are safer, and samples that last longer may be samples with the same failure point temperature but a longer time, samples with the same failure point time but a higher temperature, or samples with different failure point temperatures and times but a higher temperature.
[0298] JPEG2025503050000020.jpg250159 JPEG2025503050000021.jpg25030
[0299] JPEG2025503050000022.jpg250159 JPEG2025503050000023.jpg250117
[0300] As can be seen from Table 12, compared to the comparative example, the production examples achieved a smaller lattice change rate, a smaller Li / Mn antisite defect concentration, a larger compaction density, a surface oxygen valence closer to -2, a smaller amount of Mn and Fe eluted after fewer cycles, and better battery performance, such as better high-temperature storage performance and high-temperature cycle performance.
[0301] JPEG2025503050000024.jpg250107
[0302] As can be seen from Table 13, by doping the manganese site and phosphorus site of lithium manganese iron phosphate (manganese content 35%, phosphorus content about 20%) to form a triple-layer coating, the manganese content and the weight content ratio of manganese element and phosphorus element in the positive electrode active material are obviously reduced. Furthermore, as can be seen from comparing Preparation Examples B1 to B14 with Comparative Preparation Examples B3, B4, and B12 and combining Table 13, the reduction in manganese element and phosphorus element in the positive electrode active material reduces the amount of manganese iron elution and improves the battery performance of the secondary battery produced thereby.
[0303] JPEG2025503050000025.jpg25094
[0304] As can be seen from Table 14, by employing a first coating layer and a second coating layer containing other elements within the scope of the present application, a positive electrode active material having similarly good performance was obtained, and good battery performance results were achieved.
[0305] JPEG2025503050000026.jpg87169
[0306] As can be seen from Table 15, the angles formed by the crystal plane spacing between the first coating layer and the second coating layer of the present application were all within the range of the present application.
[0307] Consideration of the effect of the sintering method of the coating layer on the performance of the second positive electrode active material The battery preparation of the Preparation Example and Comparative Preparation Example in Table 16 is similar to Preparation Example B1, except that the method parameters in the table below are used. The results are shown in Table 16.
[0308] JPEG2025503050000027.jpg254144
[0309] As can be seen from the above, when the sintering temperature range in step S4 is 650-800°C and the sintering time is 2-6 hours, the sintering temperature range in step S6 is 500-700°C and the sintering time is 6-10 hours, and the sintering temperature range in step S8 is 700-800°C and the sintering time is 6-10 hours, a smaller lattice change rate, a smaller Li / Mn antisite defect concentration, less elution of manganese and iron elements, a better constant current charge ratio at 3C, a larger battery capacity, better battery cycle performance, and better high temperature storage stability can be achieved.
[0310] In addition, compared with Comparative Example BII-4 (wherein the sintering temperature in step S4 is 750°C and the sintering time is 4.5 hours), Example BII-1 (wherein the sintering temperature in step S4 is 750°C and the sintering time is 4 hours) achieved better positive electrode active material performance and battery performance, which indicates that when the sintering temperature in step S4 is 750°C or higher, the sintering time needs to be controlled to be shorter than 4.5 hours.
[0311] Consideration of the influence of reaction temperature and reaction time in core production on the performance of the second positive electrode active material The second positive electrode active material and battery preparation of the preparation example in the table below are similar to Preparation Example B1, and the differences in the preparation of the second positive electrode active material are shown in the method parameters in the table below. The results are also shown in the table below.
[0312] JPEG2025503050000028.jpg250118
[0313] As can be seen from Table 17, when the reaction temperature range in step S1 was 60 to 120°C and the reaction time was 2 to 9 hours, and the reaction temperature range in step S2 was 40 to 120°C and the reaction time was 1 to 10 hours, the powder performance (lattice change rate, Li / Mn antisite defect concentration, surface oxygen valence, and compaction density) of the second positive electrode active material and the performance (electric capacity, high-temperature cycle performance, and high-temperature storage performance) of the produced battery were all excellent.
[0314] JPEG2025503050000029.jpg250144
[0315] As can be seen from Table 18, As can be seen by comparing Examples 1 to 49 with Comparative Example 1, the secondary battery manufactured using the mixed positive electrode active material of the present application had a higher cycle capacity retention rate and a longer cycle life than the secondary battery manufactured using the mixed positive electrode active material of Comparative Example 1, which was manufactured by mixing a first positive electrode active material and a second positive electrode active material that were not doped with an M element.
[0316] As can be seen from a comparison between Example 16 and Examples 23 to 29, when the mass relationship m1 / (m1+m2) between the first positive electrode active material and the second positive electrode active material of the present application is between 3% and 50%, the cycle capacity retention rate of the manufactured secondary battery is further improved and the cycle life is further extended.
[0317] When the g×m1 / (m1+m2) of the first positive electrode active material and the second positive electrode active material of the present application is 0.457 or less, the cycle capacity retention rate of the manufactured secondary battery is high, the cycle life is long, and the safety is high. As can be seen from a comparison with Examples 16 and 23 to 29, when the mass relationship g×m1 / (m1+m2) of the first positive electrode active material and the second positive electrode active material of the present application is within the range of 0.025 to 0.415, the cycle capacity retention rate of the manufactured secondary battery is further improved and the cycle life is further extended.
[0318] As can be seen from a comparison of Examples 1 to 10 and 22, when the first positive electrode active material of the present application is single crystal-like, the D v When the particle size is 5.8 μm or less, the cycle capacity retention rate of the secondary battery is high, the cycle life is long, and the safety is high. v When the particle size was 4.3 μm or less, the cycle capacity retention rate of the secondary battery was further improved and the cycle life was further extended.
[0319] As can be seen from the comparison of Examples 12 to 20, when the first positive electrode active material of the present application is polycrystalline, the Dv 50 Particle size is 3.5 to 13.5 μm, and the BET specific surface area is 1.32 m 2 / g or less, and the compaction density at 3T pressure is 2.92g / cm 3 When the temperature was equal to or higher than 100° C., the cycle capacity retention rate of the produced secondary battery was higher and the cycle life was longer.
[0320] As can be seen from a comparison of Examples 1 to 8, 10 to 11, and 22, when the first positive electrode active material of the present application is single crystal-like, the first positive electrode active material LiNi b Co d Mn e M f When d in O2 was selected from the range of 0.047 to 0.235, the cycle capacity retention rate of the produced secondary battery was higher and the cycle life was longer.
[0321] The first positive electrode active material of the present application is LiNi b Co d Mn e M f When b in O2 is selected from the range of 0.314 to 0.970, the cycle capacity retention rate of the manufactured secondary battery is high, the cycle life is long, and the safety is high. As can be seen from comparing Examples 1 to 7, 9 to 11, and 22, when the first positive electrode active material is a single crystal or pseudo single crystal material, when b is greater than 0.314 and less than 0.97 (excluding the values of 0.314 and 0.97), the cycle capacity retention rate of the manufactured secondary battery is higher and the cycle life is longer.
[0322] As can be seen from a comparison between Examples 10 and 22, when the mass content of lithium carbonate in the first positive electrode active material of the present application was 1% or less and the mass content of lithium hydroxide was 1% or less, the cycle capacity retention rate of the produced secondary battery was higher and the cycle life was longer.
[0323] As can be seen by comparing Tables 11 and 18, Compared with secondary batteries produced using the first positive electrode active material, the secondary batteries produced using the mixed positive electrode active material containing the first positive electrode active material of the present application had higher safety, and compared with secondary batteries produced using the first positive electrode active materials of Production Examples A5, A14 to A17, and A19 to A21, the secondary batteries produced using the mixed positive electrode active material containing the first positive electrode active material of the present application had higher cycle capacity retention and longer cycle life.
[0324] As can be seen by comparing Tables 12 to 17 with Table 18, Compared with the secondary batteries manufactured using the second positive electrode active materials of Manufacturing Examples B26 to B28, B15, B34, B4, B7, B8, B31, B40, B42, BIII-13, B43, Manufacturing Examples B46 to B48, and Manufacturing Example B52, the secondary batteries manufactured using the mixed positive electrode active material containing the corresponding second positive electrode active material of the present application had higher cycle capacity retention rates and longer cycle lives.
[0325] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is an example, and any embodiment having substantially the same configuration as the technical idea and the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]
[0326] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate.
Claims
1. A positive electrode active material including a first positive electrode active material and a second positive electrode active material, The first positive electrode active material is the compound LiNi g Co d Mn e M' f O 2 wherein g is selected from the range of 0.314 to 0.970, d is selected from the range of 0 to 0.320, optionally selected from the range of 0.047 to 0.320, e is selected from the range of 0.006 to 0.390, the sum of g, d, e and f is 1 and f is greater than 0, M' is one or more elements selected from Mn, Al, Mg, Ca, Na, Ti, W, Zr, Sr, Cr, Zn, Ba, B, S and Y, optionally M' is Mg and / or Al; The second positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the core is a compound Li 1+x Mn 1-y A y P 1-z R z O 4 The first coating layer comprises crystalline Li pyrophosphate. a MP 2 O 7 and / or M b (P 2 O 7 ) c The second coating layer comprises a crystalline phosphate X n P.O. 4 and the third coating layer comprises carbon, wherein x is selected from the range of -0.100 to 0.100, y is selected from the range of 0.001 to 0.909, optionally selected from the range of 0.001 to 0.600, z is selected from the range of 0.001 to 0.100, a is greater than 0 and less than or equal to 2, b is greater than 0 and less than or equal to 4, c is greater than 0 and less than or equal to 3, and n is 0. and not greater than 3, A being one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, and optionally one or more elements of Fe, V, Ni, and Co, R being one or more elements selected from B, Si, N, and S, and optionally one or more elements selected from Si, N, and S, and the crystalline pyrophosphate Li a MP 2 O 7 and M. b (P 2 O 7 ) c each M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Fe, Co, Ti, and Al; and each X is independently one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Li, Fe, Ag, and Al.
2. The mass of the first positive electrode active material is m 1 and the mass of the second positive electrode active material is m 2 And m 1 / (m 1 +m 2 2. The cathode active material of claim 1, wherein the value of is 2% to 55%, and optionally 3% to 50%.
3. g x m 1 / (m 1 +m 2 3. The positive electrode active material according to claim 1, wherein the value of is 0.017 to 0.457, and optionally 0.025 to 0.
415.
4. The first positive electrode active material is a single crystal or pseudo single crystal material, and the particle size D of the first positive electrode active material is v 4. The positive electrode active material according to claim 1, wherein 50 is 5.8 μm or less, optionally 2.3 to 5.8 μm, and further optionally 2.3 to 4.3 μm.
5. When the first positive electrode active material is a single crystal or pseudo-single crystal material, and / or, d is selected from the range of 0.047 to 0.320, optionally selected from the range of 0.05 to 0.235; The positive electrode active material according to any one of claims 1 to 4, wherein b is greater than 0.314 and less than 0.97, and is selectively selected from the range of 0.55 to 0.
869.
6. When the first positive electrode active material is a polycrystalline material, the particle diameter D of the first positive electrode active material v 50 is 3.0 to 13.5 μm, optionally 3.5 to 13.5 μm; and / or The BET specific surface area of the first positive electrode active material is 1.73 m 2 / g or less, and optionally 1.32 m 2 / g or less, and more preferably 0.28 to 1.32 m 2 / g, and / or The compaction density of the first positive electrode active material at a pressure of 3 T is 2.90 g / cm 3 or more, and optionally 2.92 g / cm 3 or more, and more selectively, 2.92 to 3.31 g / cm 3 The positive electrode active material according to claim 1 ,
7. The first positive electrode active material further contains lithium carbonate and / or lithium hydroxide, 7. The cathode active material according to claim 1, wherein the mass content of the lithium carbonate is 1.05% or less, and optionally 1% or less, and / or the mass content of the lithium hydroxide is 1.02% or less, and optionally 1% or less, based on the mass of the first cathode active material.
8. 8. The cathode active material of claim 1, wherein in the core, the ratio of y to 1-y is from 1:10 to 10:1, optionally from 1:4 to 1:
1.
9. 9. The cathode active material of claim 1, wherein in the core, the ratio of z to 1-z is from 1:999 to 1:9, optionally from 1:499 to 1:
249.
10. the carbon in the third coating layer is a mixture of SP2 and SP3 carbon forms; 10. The positive electrode active material according to claim 1, wherein the molar ratio of the SP2 carbon to the SP3 carbon is preferably 0.1 to 10, and more preferably 2.0 to 3.
0.
11. The coating amount of the first coating layer is, based on the weight of the core, greater than 0 and less than 6 wt%, alternatively greater than 0 and less than 5.5 wt%, and further alternatively greater than 0 and less than 2 wt%, and / or The amount of the second coating layer is, based on the weight of the core, greater than 0 and less than 6 wt%, alternatively greater than 0 and less than 5.5 wt%, and further alternatively 2 to 4 wt%, and / or 11. The positive electrode active material according to claim 1, wherein the coating amount of the third coating layer is greater than 0 and less than 6 wt%, selectively greater than 0 and less than 5.5 wt%, and further selectively greater than 0 and less than 2 wt%, based on the weight of the core.
12. the thickness of the first coating layer is between 2 and 10 nm; and / or the thickness of the second coating layer is between 2 and 15 nm, optionally between 2.5 and 7.5 nm; and / or The positive electrode active material according to any one of claims 1 to 11, wherein the third coating layer has a thickness of 5 to 25 nm.
13. In the second positive electrode active material, the crystal plane spacing range of the crystalline pyrophosphate in the first coating layer is 0.293 to 0.470 nm, and optionally 0.303 to 0.462 nm, and the angle range of the crystal orientation (111) is 18.00° to 32.00°, and optionally 19.211° to 30.846°, and / or The crystal plane spacing range of the crystalline phosphate in the second coating layer is 0.244 to 0.425 nm, and the angle range of the crystal orientation (111) is 20.00 ° to 37.00 °, and optionally 20.885 ° to 36.808 °. The positive electrode active material according to any one of claims 1 to 12.
14. Based on the weight of the second positive electrode active material, the content of manganese element is in the range of 10 wt% to 35 wt%, optionally in the range of 15 wt% to 30 wt%, and further optionally in the range of 17 wt% to 20 wt%, and / or The content of phosphorus element is in the range of 12% to 25% by weight, optionally in the range of 15% to 20% by weight, and / or The cathode active material according to any one of claims 1 to 13, wherein the weight ratio range of elemental manganese to elemental phosphorus is 0.90 to 1.25, and optionally 0.95 to 1.
20.
15. The lattice change rate of the second positive electrode active material before and after complete release of lithium is 4% or less, optionally 3.8% or less, and further optionally 2.0 to 3.8%. The positive electrode active material according to any one of claims 1 to 14.
16. The positive electrode active material according to any one of claims 1 to 15, wherein the Li / Mn antisite defect concentration of the second positive electrode active material is 4% or less, optionally 2.2% or less, and further optionally 1.5 to 2.2%.
17. The compaction density of the second positive electrode active material at 3 T is 2.2 g / cm 3 or more, and optionally 2.2 g / cm 3 or more and 2.8 g / cm 3 The positive electrode active material according to any one of claims 1 to 16, wherein:
18. The cathode active material according to any one of claims 1 to 17, wherein the surface oxygen valence of the second cathode active material is -1.90 or less, and optionally -1.90 to -1.
98.
19. A method for producing a positive electrode active material, comprising the steps of: providing a first active cathode material and a second active cathode material; mixing the first positive electrode active material with the second positive electrode active material; The first positive electrode active material is the compound LiNi g Co d Mn e M' f O 2 The second positive electrode active material includes a core and a shell covering the core, the shell includes a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the core is a compound Li 1+x Mn 1-y A y P 1-z R z O 4 The first coating layer comprises crystalline Li pyrophosphate. a MP 2 O 7 and / or M b (P 2 O 7 ) c The second coating layer comprises a crystalline phosphate X n P.O. 4 and the third coating layer comprises carbon, wherein the definitions of g, d, e, f, x, y, z, a, b, c, n, A, R, M, X and M' are as defined in any one of claims 1 to 18, Optionally, the first active cathode material further comprises lithium carbonate and / or lithium hydroxide.
20. A positive electrode plate comprising: a positive electrode current collector; and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode active material according to any one of claims 1 to 18 or the positive electrode active material produced by the method according to claim 19, and optionally, a content of the positive electrode active material in the positive electrode film layer is 10 wt % or more, and further optionally, 95 to 99.5 wt %, based on a total weight of the positive electrode film layer.
21. A secondary battery comprising the positive electrode active material according to any one of claims 1 to 18, or the positive electrode active material produced by the method according to claim 19, or the positive electrode plate according to claim 20.
22. A battery module comprising the secondary battery according to claim 21.
23. A battery pack comprising the battery module of claim 22.
24. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 21, the battery module according to claim 22, and the battery pack according to claim 23.
Citation Information
Patent Citations
Security lithium ion battery positive plate as well as preparation method thereof
CN103811727A
Lithium ion battery positive electrode material with adjustable crystalline grain size and preparation method thereof
CN105118985A
Lithium manganese iron phosphate composite material, preparation method thereof and lithium ion battery
CN114256448A
Positive electrode active material and nonaqueous electrolyte secondary battery
JP2002198050A
Nonaqueous electrolyte secondary battery
JP2010129332A